Acute care and secondary prevention of stroke with newly detected versus known atrial fibrillation - Wang, Ruihao; Macha, Kosmas; Haupenthal, David; Gaßmann, Luise; Siedler, Gabriela; Stoll, Svenja; Fröhlich, Kilian; Köhn, Julia; Schwab, Stefan; Kallmünzer, Bernd (European Journal of Neurology, 2022)
Background and purpose: Atrial fibrillation (AF) in stroke patients can be classified as either “known AF” (KAF), defined as AF confirmed before stroke onset, or “AF detected after stroke” (AFDAS), defined as AF diagnosed after stroke onset. While KAF is considered primarily cardiogenic, AFDAS includes patients with stroke-triggered neurogenic arrhythmias. This study aimed to investigate the clinical course of stroke, functional outcomes and the value of oral anticoagulation (OAC) for secondary prevention according to AF subtype. Methods: Acute ischemic stroke patients were consecutively enrolled and AF was classified as AFDAS or KAF. Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) and 3-month functional outcomes were measured on the modified Rankin scale. Inverse probability weighting was applied to adjust for baseline confounders in patients with AFDAS and KAF. Multivariate logistic regression models were calculated to investigate the value of OAC for secondary prevention. Results: A total of 822 stroke patients with AF were included, of whom 234 patients (28.5%) had AFDAS. AFDAS patients had a lower prevalence of coronary artery disease, heart failure, and sustained AF, but higher rates of large vessel occlusion compared to KAF patients. NIHSS scores were lower in patients on pre-stroke anticoagulation. OAC for secondary prevention was associated with favorable 3-month functional outcome (odds ratio 7.60, 95% confidence interval 3.42–16.88) independently of AF subtype. The rate of stroke recurrence did not differ significantly. Conclusions: Clinical characteristics suggest that AFDAS might comprise a distinct pathophysiological and clinical entity among stroke patients with AF. The benefit of anticoagulation for secondary prevention was not affected by AF subtype.
CRIS-Team Scopus Importer:2022-04-22
Keywords: acute ischemic stroke; atrial fibrillation detected after stroke; known atrial fibrillation; modified Rankin scale; oral anticoagulation; stroke recurrence

Acute right insular ischaemic lesions and poststroke left ventricular dysfunction - Winder, Klemens; Villegas Millar, Carolina; Siedler, Gabriela; Knott, Michael; Dörfler, Arnd; Engel, Anna; Achenbach, Stephan; Hilz, Max-Josef; Kallmünzer, Bernd; Schwab, Stefan; Seifert, Frank; Fröhlich, Kilian (Stroke and Vascular Neurology, 2023)
IntroductionMyocardial injury related to acute ischaemic stroke is common even without primary cardiac disease. We intended to determine associations between values of left ventricular ejection fraction (LVEF) and ischaemic stroke lesion sites. MethodsOf a local database, patients with acute first-ever ischaemic stroke confirmed by brain imaging but without pre-existing heart disease were included. The cardiac morphology and LVEF were obtained from transthoracic or transesophageal echocardiography, and impaired LVEF was categorised as mild (35%-50%), moderate (34%-25%) and severe (<25%). Patient age, stroke severity, ischaemic lesion volume, prevalence of troponin I increase (>0.1 ng/mL), atrial fibrillation and cardiac wall motion abnormalities were assessed and compared between patients with and without impaired LVEF after stroke (significance: p<0.05). A multivariate voxelwise lesion analysis correlated LVEF after stroke with sites of ischaemic lesions. ResultsOf 1209 patients who had a stroke, 231 (mean age 66.3 +/- 14.0 years) met the inclusion criteria; 40 patients (17.3%) had an impaired LVEF after stroke. Patients with impaired LVEF had higher infarct volumes (53.8 mL vs 30.0 mL, p=0.042), a higher prevalence of troponin increase (17.5% vs 4.2%, p=0.006), cardiac wall motion abnormalities (42.5% vs 5.2%, p<0.001) and atrial fibrillation (60.0% vs 26.2%, p<0.001) than patients with LVEF of >50%. The multivariate voxelwise lesion analysis yielded associations between decreased LVEF and damaged voxels in the insula, amygdala and operculum of the right hemisphere. ConclusionOur imaging analysis unveils a prominent role of the right hemispheric central autonomic network, especially of the insular cortex, in the brain-heart axis. Our results support preliminary evidence that acute ischaemic stroke in distinct brain regions of the central autonomic network may directly impair cardiac function and thus further supports the concept of a distinct stroke-heart syndrome.
CRIS-Team WoS Importer:2023-02-24

Acute Stroke in Times of the COVID-19 Pandemic: A Multicenter Study - Hoyer, Carolin; Ebert, Anne; Huttner, Hagen; Puetz, Volker; Kallmünzer, Bernd; Barlinn, Kristian; Haverkamp, Christian; Harloff, Andreas; Brich, Jochen; Platten, Michael; Szabo, Kristina (Stroke, 2020)
Background and Purpose: This study aims to assess the number of patients with acute ischemic cerebrovascular events seeking in-patient medical emergency care since the implementation of social distancing measures in the coronavirus disease 2019 (COVID-19) pandemic. Methods: In this retrospective multicenter study, data on the number of hospital admissions due to acute ischemic stroke or transient ischemic attack and numbers of reperfusion therapies performed in weeks 1 to 15 of 2020 and 2019 were collected in 4 German academic stroke centers. Poisson regression was used to test for a change in admission rates before and after the implementation of extensive social distancing measures in week 12 of 2020. The analysis of anonymized regional mobility data allowed for correlations between changes in public mobility as measured by the number and length of trips taken and hospital admission for stroke/transient ischemic attack. Results: Only little variation of admission rates was observed before and after week 11 in 2019 and between the weeks 1 and 11 of 2019 and 2020. However, reflecting the impact of the COVID-19 pandemic, a significant decrease in the number of admissions for transient ischemic attack was observed (-85%, -46%, -42%) in 3 of 4 centers, while in 2 of 4 centers, stroke admission rates decreased significantly by 40% and 46% after week 12 in 2020. A relevant effect on reperfusion therapies was found for 1 center only (thrombolysis, -60%; thrombectomy, -61%). Positive correlations between number of ischemic events and mobility measures in the corresponding cities were identified for 3 of 4 centers. Conclusions: These data demonstrate and quantify decreasing hospital admissions due to ischemic cerebrovascular events and suggest that this may be a consequence of social distancing measures, in particular because hospital resources for acute stroke care were not limited during this period. Hence, raising public awareness is necessary to avoid serious healthcare and economic consequences of undiagnosed and untreated strokes and transient ischemic attacks.
CRIS-Team Scopus Importer:2020-07-10
Keywords: brain ischemia; pandemics; reperfusion; stroke; thrombectomy

Acute Stroke With Large Vessel Occlusion and Minor Clinical Deficits: Prognostic Factors and Therapeutic Implications - Volbers, Bastian; Gröger, Rebecca; Engelhorn, Tobias; Marsch, Armin; Macha, Kosmas; Schwab, Stefan; Dörfler, Arnd; Lang, Stefan; Kallmünzer, Bernd (Frontiers in Neurology, 2021)
Background and Purpose: The optimal acute management of patients with large vessel occlusion (LVO) and minor clinical deficits on admission [National Institutes of Health Stroke Scale (NIHSS) <= 4] remains to be elucidated. The aim of the present study was to investigate the prognostic factors and therapeutic management of those patients.
CRIS-Team WoS Importer:2021-11-19

Aetiology, secondary prevention strategies and outcomes of ischaemic stroke despite oral anticoagulant therapy in patients with atrial fibrillation - Polymeris, Alexandros A.; Meinel, Thomas R.; Oehler, Hannah; Hoelscher, Kyra; Zietz, Annaelle; Scheitz, Jan F.; Nolte, Christian H.; Stretz, Christoph; Yaghi, Shadi; Stoll, Svenja; Wang, Ruihao; Haeusler, Karl Georg; et al. (Journal of Neurology Neurosurgery and Psychiatry, 2022)
Objective To investigate the aetiology, subsequent preventive strategies and outcomes of stroke despite anticoagulation in patients with atrial fibrillation (AF).
CRIS-Team WoS Importer:2022-04-22

Amantadine treatment is associated with improved consciousness in patients with non-traumatic brain injury - Ruehl, Lena; Kuramatsu, Joji; Sembill, Jochen; Kallmünzer, Bernd; Madzar, Dominik; Gerner, Stefan; Giede-Jeppe, Antje; Balk, Stefanie; Müller, Tamara; Jäger, Jakob; Schwab, Stefan; Huttner, Hagen; et al. (Journal of Neurology Neurosurgery and Psychiatry, 2022)
Objective This study determined the effect of amantadine treatment on consciousness in patients with non-traumatic brain injury. Methods We pooled individual patient data of five single-centre observational studies to determine the effect of amantadine treatment among patients with ischaemic stroke, intracerebral haemorrhage, subarachnoid haemorrhage, community-acquired bacterial meningitis and status epilepticus, admitted between January 2012 and December 2015 and ventilated >= 7 days. Patient selection and multivariable regression modelling were used to adjust for differences in intergroup comparison and for parameters associated with consciousness. Improvement of consciousness 5 days after treatment initiation was defined as primary outcome. Secondary outcomes included Glasgow Coma Scale (GCS) at day 5 and GCS at day 10, rate of ICU delirium, epileptic seizures and all-cause mortality at 90 days. Results Overall, 84 of 294 (28.6%) eligible patients received amantadine. Amantadine treatment was associated with improvement of consciousness at day 5 (amantadine: 86.9% vs control: 54.0%; absolute difference: 32.9 (20.0-44.2); adjusted OR (aOR): 5.71 (2.50-13.05), p<0.001). Secondary outcomes showed differences in GCS 5 days (9 (8-11) vs 6 (3-9), p<0.001) and GCS 10 days (10(8-11) vs 9(6-11),p=0.003) after treatment initiation. There were no significant differences regarding all-cause mortality (aOR: 0.89 (0.44-1.82), p=0.758) and ICU delirium (aOR: 1.39 (0.58-3.31), p=0.462). Rate of epileptic seizures after initiation of amantadine treatment was numerically higher in the amantadine group (amantadine: 10.7% vs control: 3.0%; absolute difference: 7.7 (0.3-16.4); aOR: 3.68 (0.86-15.71), p=0.079). Conclusions Amantadine treatment is associated with improved consciousness among patients with different types of non-traumatic brain injury in this observational cohort analysis. Epileptic seizures should be considered as potential side effects and randomised controlled trials are needed to confirm these findings.
CRIS-Team WoS Importer:2022-02-11

Andexanet for Factor Xa Inhibitor-Associated Acute Intracerebral Hemorrhage - Connolly, Stuart J.; Sharma, Mukul; Cohen, Alexander T.; Demchuk, Andrew M.; Członkowska, Anna; Lindgren, Arne G.; Molina, Carlos A.; Bereczki, Daniel; Toni, Danilo; Seiffge, David J.; Tanne, David; Sandset, Else Charlotte; et al. (New England Journal of Medicine, 2024)
Background Patients with acute intracerebral hemorrhage who are receiving factor Xa inhibitors have a risk of hematoma expansion. The effect of andexanet alfa, an agent that reverses the effects of factor Xa inhibitors, on hematoma volume expansion has not been well studied. Methods We randomly assigned, in a 1:1 ratio, patients who had taken factor Xa inhibitors within 15 hours before having an acute intracerebral hemorrhage to receive andexanet or usual care. The primary end point was hemostatic efficacy, defined by expansion of the hematoma volume by 35% or less at 12 hours after baseline, an increase in the score on the National Institutes of Health Stroke Scale of less than 7 points (scores range from 0 to 42, with higher scores indicating worse neurologic deficit) at 12 hours, and no receipt of rescue therapy between 3 hours and 12 hours. Safety end points were thrombotic events and death. Results A total of 263 patients were assigned to receive andexanet, and 267 to receive usual care. Efficacy was assessed in an interim analysis that included 452 patients, and safety was analyzed in all 530 enrolled patients. Atrial fibrillation was the most common indication for factor Xa inhibitors. Of the patients receiving usual care, 85.5% received prothrombin complex concentrate. Hemostatic efficacy was achieved in 150 of 224 patients (67.0%) receiving andexanet and in 121 of 228 (53.1%) receiving usual care (adjusted difference, 13.4 percentage points; 95% confidence interval [CI], 4.6 to 22.2; P=0.003). The median reduction from baseline to the 1-to-2-hour nadir in anti-factor Xa activity was 94.5% with andexanet and 26.9% with usual care (P<0.001). Thrombotic events occurred in 27 of 263 patients (10.3%) receiving andexanet and in 15 of 267 (5.6%) receiving usual care (difference, 4.6 percentage points; 95% CI, 0.1 to 9.2; P=0.048); ischemic stroke occurred in 17 patients (6.5%) and 4 patients (1.5%), respectively. There were no appreciable differences between the groups in the score on the modified Rankin scale or in death within 30 days. Conclusions Among patients with intracerebral hemorrhage who were receiving factor Xa inhibitors, andexanet resulted in better control of hematoma expansion than usual care but was associated with thrombotic events, including ischemic stroke. (Funded by Alexion AstraZeneca Rare Disease and others; ANNEXA-I ClinicalTrials.gov number, NCT03661528.).
CRIS-Team Scopus Importer:2024-05-31
Keywords: Coagulation; Emergency Medicine; Emergency Medicine General; Hematology/Oncology; Neurology/Neurosurgery; Stroke; Stroke

Angioedema in Stroke Patients With Thrombolysis - Fröhlich, Katharina; Macha, Kosmas; Gerner, Stefan; Bobinger, Tobias; Schmidt, Manuel; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Seifert, Frank; Kallmünzer, Bernd; Winder, Klemens (Stroke, 2019)
Background and Purpose- Oral angioedema (OA) is a rare but life-threatening complication in patients with ischemic stroke receiving intravenous thrombolysis with r-tPA (recombinant tissue-type plasminogen activator). This study intended to determine associations between thrombolysis-related OA and ischemic stroke lesion sites using a voxel-wise lesion analysis. Methods- Prospective registry data were used to identify ischemic stroke patients with thrombolysis-related OA between 2002 and 2018. For the study registry, ethics approval was obtained by the Ethics Committee of the Friedrich-Alexander Universität (FAU) Erlangen-Nürnberg (clinical registry registration: 377_17Bc). Ischemic stroke patients with thrombolysis treatment but without OA admitted in the years 2011 and 2012 comprised the control group. Ischemic lesions were manually outlined on magnetic resonance imaging (1.5T or 3T) or computed tomographic scans and transformed into stereotaxic space. We determined the lesion overlap and compared the absence or presence of OA voxel-wise between patients with and without lesions in a given voxel using the Liebermeister test. Stroke severity was rated using the National Institutes of Health Stroke Scale score, and blood pressure, heart rate, blood glucose levels, and body temperature were determined on admission. Results- Fifteen ischemic stroke patients with thrombolysis-related OA were identified. The voxel-wise analysis yielded associations between OA and ischemic lesions in the insulo-opercular region with a right hemispheric dominance. Mean blood pressure was significantly lower in patients with OA than in controls. Age, National Institutes of Health Stroke Scale scores, infarct volumes, heart rate, and blood glucose levels did not differ between patients with and without OA. Conclusions- The voxel-wise analysis linked thrombolysis-related OA to right insulo-opercular lesions. The lower blood pressure in patients with thrombolysis-related OA may reflect bradykinin effects causing vasodilatation and increasing vascular permeability.
CRIS-Team Scopus Importer:2019-07-19
Keywords: angioedema; autonomic nervous system; brain ischemia; neuroimaging; stroke; tissue-type plasminogen activator

Association of non-contrast CT markers with long-term functional outcome in deep intracerebral hemorrhage. - Kölbl, Kathrin; Hock, Stefan; Xu, Mingming; Sembill, Jochen; Mrochen, Anne; Balk, Stefanie; Lang, Stefan; Volbers, Bastian; Engelhorn, Tobias Martin; Kallmünzer, Bernd; Kuramatsu, Joji (Frontiers in Neurology, 2024)
OBJECTIVE: Hematoma expansion (HE) is the most important therapeutic target during acute care of patients with intracerebral hemorrhage (ICH). Imaging biomarkers such as non-contrast CT (NCCT) markers have been associated with increasing risk for HE. The aim of the present study was to evaluate the influence of NCCT markers with functional long-term outcome and with HE in patients with deep (basal ganglia and thalamus) ICH who represent an important subgroup of patients at the highest risk for functional deterioration with HE due to the eloquence of the affected brain region. METHODS: From our prospective institutional database, all patients maximally treated with deep ICH were included and retrospectively analyzed. NCCT markers were recorded at diagnostic imaging, ICH volume characteristics were volumetrically evaluated, and all patients received follow-up imaging within 0-48 h. We explored associations of NCCT makers with unfavorable functional outcome, defined as modified Rankin scale 4-6, after 12 months and with HE. Bias and confounding were addressed by multivariable regression modeling. RESULTS: In 322 patients with deep ICH, NCCT markers were distributed as follows: irregular shape: 69.6%, heterogenous density: 55.9%, hypodensities: 52.5%, island sign: 19.3%, black hole sign: 11.5%, and blend sign: 4.7%. Upon multivariable regression analyses, independent associations were documented with the functional outcome for irregular shape (aOR: 2.73, 95%CI: 1.42-5.22, p = 0.002), heterogenous density (aOR: 2.62, 95%CI: 1.40-4.90, p = 0.003) and island sign (aOR: 2.54, 95%CI: 1.05-6.14, p = 0.038), and with HE for heterogenous density (aOR: 5.01, 95%CI: 1.93-13.05, p = 0.001) and hypodensities (aOR: 3.75, 95%CI: 1.63-8.62, p = 0.002). CONCLUSION: NCCT markers are frequent in deep ICH patients and provide important clinical implications. Specifically, markers defined by diverging intra-hematomal densities provided associations with a 5-times higher risk for HE and a 2.5-times higher likelihood for unfavorable functional long-term outcome. Hence, these markers allow the identification of patients with deep ICH at high risk for clinical deterioration due to HE.
EVALuna2:552372

Atrial Fibrillation Detected before or after Stroke: Role of Anticoagulation - Lyrer, Flurina; Zietz, Annaelle; Seiffge, David J.; Koga, Masatoshi; Volbers, Bastian; Wilson, Duncan; Bonetti, Bruno; Schaedelin, Sabine; Gensicke, Henrik; Yoshimura, Sohei; Macha, Kosmas; Ambler, Gareth; et al. (Annals of Neurology, 2023)
Background: Atrial fibrillation (AF) known before ischemic stroke (KAF) has been postulated to be an independent category with a recurrence risk higher than that of AF detected after stroke (AFDAS). However, it is unknown whether this risk difference is confounded by pre-existing anticoagulation, which is most common in KAF and also indicates a high ischemic stroke recurrence risk. Methods: Individual patient data analysis from 5 prospective cohorts of anticoagulated patients following AF-associated ischemic stroke. We compared the primary (ischemic stroke recurrence) and secondary outcome (all-cause death) among patients with AFDAS versus KAF and among anticoagulation-naïve versus previously anticoagulated patients using multivariable Cox, Fine-Gray models, and goodness-of-fit statistics to investigate the relative independent prognostic importance of AF-category and pre-existing anticoagulation. Results: Of 4,357 patients, 1,889 (43%) had AFDAS and 2,468 (57%) had KAF, while 3,105 (71%) were anticoagulation-naïve before stroke and 1,252 (29%) were previously anticoagulated. During 6,071 patient-years of follow-up, we observed 244 recurrent strokes and 661 deaths. Only pre-existing anticoagulation (but not KAF) was independently associated with a higher hazard for stroke recurrence in both Cox and Fine-Gray models. Models incorporating pre-existing anticoagulation showed better fit than those with AF category; adding AF-category did not result in better model fit. Neither pre-existing anticoagulation nor KAF were independently associated with death. Conclusion: Our findings challenge the notion that KAF and AFDAS are clinically relevant and distinct prognostic entities. Instead of attributing an independently high stroke recurrence risk to KAF, future research should focus on the causes of stroke despite anticoagulation to develop improved preventive treatments. ANN NEUROL 2023.
CRIS-Team Scopus Importer:2023-04-28

Author Response: Multimodal CT or MRI for IV Thrombolysis in Ischemic Stroke With Unknown Time of Onset. - Macha, Kosmas; Hölter, Philip; Kallmünzer, Bernd (Neurology, 2021)
EVALuna2:470177

Blood biomarker changes following therapeutic hypothermia in ischemic stroke - Palà, Elena; Penalba, Anna; Bustamante, Alejandro; García-Berrocoso, Teresa; Lamana-Vallverdú, Marcel; Meisel, Christian; Meisel, Andreas; van der Worp, H. Bart; R Macleod, Malcolm; Kallmünzer, Bernd; Schwab, Stefan; Montaner, Joan (Brain and Behavior, 2023)
Introduction: Therapeutic hypothermia is a promising candidate for stroke treatment although its efficacy has not yet been demonstrated in patients. Changes in blood molecules could act as surrogate markers to evaluate the efficacy and safety of therapeutic cooling. Methods: Blood samples from 54 patients included in the EuroHYP-1 study (27 treated with hypothermia, and 27 controls) were obtained at baseline, 24 ± 2 h, and 72 ± 4 h. The levels of a panel of 27 biomarkers, including matrix metalloproteinases and cardiac and inflammatory markers, were measured. Results: Metalloproteinase-3 (MMP-3), fatty-acid-binding protein (FABP), and interleukin-8 (IL-8) increased over time in relation to the hypothermia treatment. Statistically significant correlations between the minimum temperature achieved by each patient in the hypothermia group and the MMP-3 level measured at 72 h, FABP level measured at 24 h, and IL-8 levels measured at 24 and 72 h were found. No differential biomarker levels were observed in patients with poor or favorable outcomes according to modified Rankin Scale scores. Conclusion: Although the exact roles of MMP3, FABP, and IL-8 in hypothermia-treated stroke patients are not known, further exploration is needed to confirm their roles in brain ischemia.
CRIS-Team Scopus Importer:2023-09-29
Keywords: biomarkers; hypothermia; ischemia; stroke

Cardiovascular autonomic dysfunction in patients with posterior circulation ischemic stroke - Wang, Ruihao; Macha, Kosmas; Koehn, Julia; Siedler, Gabriela; Winder, Klemens; Gerner, Stefan; Schwab, Stefan; Kohrmann, Martin; Hilz, Max-Josef; Kallmünzer, Bernd (JOURNAL OF THE NEUROLOGICAL SCIENCES, 2021)
CRIS-Team WoS Importer:2021-12-03

CARDIOVASCULAR AUTONOMIC MODULATION THREE MONTHS POST STROKE IMPROVES IN PATIENTS WITH ISCHEMIA IN THE RIGHT MIDDLE CEREBRAL ARTERY TERRITORY - Wang, Ruihao; Macha, Kosmas; Köhn, Julia; Marsch, Armin; Winder, Klemens; Gerner, Stefan; Koehrmann, M.; Schwab, Stefan; Kallmünzer, Bernd; Hilz, Max-Josef (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Cardiovascular medication seems to promote recovery of autonomic dysfunction after stroke - Wang, Ruihao; Koehrmann, Martin; Kollmar, Rainer; Köhn, Julia; Schwab, Stefan; Kallmünzer, Bernd; Hilz, Max-Josef (Journal of Neurology, 2022)
Background Stroke may compromise cardiovascular-autonomic modulation (CAM). The longitudinal post-stroke CAM alterations remain unclear as previous studies excluded patients with cardiovascular medication. This study evaluated whether CAM dysfunction improves after several months in patients under typical clinical conditions, i.e., without excluding patients with cardiovascular medication. Methods In 82 ischemic stroke patients [33 women, 64.9 +/- 8.9 years, NIHSS-scores 2 (interquartile range 1-5)], we evaluated the applications of cardiovascular medication before stroke, during autonomic tests performed within 1 week, 3 and 6 months after stroke onset. We determined resting RR intervals (RRI), systolic, diastolic blood pressures (BPsys), respiration, parameters reflecting total CAM [RRI-standard deviation (RRI-SD), RRI-total powers], sympathetic [RRI-low-frequency powers (RRI-LF), BPsys-LF powers] and parasympathetic CAM [RMSSD, RRI-high-frequency powers (RRI-HF powers)], and baroreflex sensitivity. ANOVA or Friedman tests with post hoc analyses compared patient data with data of 30 healthy controls, significance was assumed for P < 0.05. Results More patients had antihypertensive medication after than before stroke. First-week CAM testing showed lower RRIs, RMSSD, RRI-SDs, RRI-total powers, RRI-HF powers, and baroreflex sensitivity, but higher BPsys-LF powers in patients than controls. After 3 and 6 months, patients had significantly higher RRIs, RRI-SDs, RRI-total powers, RMSSDs, RRI-HF powers, and baroreflex sensitivity, but lower BPsys-LF powers than in the 1st week; RMSSDs and RRI-HF powers no longer differed between patients and controls. However, 6-month values of RRIs, RRI-SDs, and baroreflex sensitivity were again lower in patients than controls. Conclusions Even mild strokes compromised cardiovagal modulation and baroreflex sensitivity. After 3 months, CAM had almost completely recovered. Recovery might be related to the mild stroke severity. Presumably, CAM recovery was also promoted by the increased application of cardiovascular medication. Yet, slight CAM dysfunction after 6 months suggests continuing autonomic vulnerability.
CRIS-Team WoS Importer:2022-06-24

Cerebral Ischemia in Patients on Direct Oral Anticoagulants - Macha, Kosmas; Marsch, Armin; Siedler, Gabriela; Breuer, Lorenz; Strasser, Erwin; Engelhorn, Tobias; Schwab, Stefan; Kallmünzer, Bernd (Stroke, 2019)
Background and Purpose- In patients with ischemic stroke on therapy with vitamin K antagonists, stroke severity and clinical course are affected by the quality of anticoagulation at the time of stroke onset, but clinical data for patients using direct oral anticoagulants (DOACs) are limited. Methods- Data from our registry including all patients admitted with acute cerebral ischemia while taking oral anticoagulants for atrial fibrillation between November 2014 and October 2017 were investigated. The activity of vitamin K antagonists was assessed using the international normalized ratio on admission and categorized according to a threshold of 1.7. DOAC plasma levels were measured using the calibrated Xa-activity (apixaban, rivaroxaban, and edoxaban) or the Hemoclot-assay (dabigatran) and categorized into low (<50 ng/mL), intermediate (50-100 ng/mL), or high (>100 ng/mL). Primary objective was the association between anticoagulant activity and clinical and imaging characteristics. Results- Four hundred sixty patients were included (49% on vitamin K antagonists and 51% on DOAC). Patients on vitamin K antagonists with low international normalized ratio values had higher scores on the National Institutes of Health Stroke Scale and a higher risk of large vessel occlusion on admission. For patients on DOAC, plasma levels were available in 75.6% and found to be low in 49 (27.7%), intermediate in 41 (23.2%), and high in 87 patients (49.2%). Low plasma levels were associated with higher National Institutes of Health Stroke Scale scores on admission (low: 8 [interquartile range, 3-15] versus intermediate: 4 [1-11] versus high: 3 [0-8]; P<0.001) and higher risk of persisting neurological deficits or cerebral infarction on imaging (85.7% versus 75.6% versus 54.0%; P<0.001). Low DOAC plasma levels were an independent predictor of large vessel occlusion (odds ratio, 3.84 [95% CI, 1.80-8.20]; P=0.001). Conclusions- The activity of anticoagulation measured by specific DOAC plasma levels on admission is associated with stroke severity and presence of large vessel occlusion.
CRIS-Team Scopus Importer:2019-07-19
Keywords: anticoagulants; atrial fibrillation; direct oral anticoagulants; ischemic stroke; plasma level

Comparison of Two Automated Computed Tomography Perfusion Applications to Predict the Final Infarct Volume After Thrombolysis in Cerebral Infarction 3 Recanalization - Mühlen, Iris; Sprügel, Maximilian; Hölter, Philip; Hock, Stefan; Knott, Michael; Huttner, Hagen; Schwab, Stefan; Kallmünzer, Bernd; Dörfler, Arnd (Stroke, 2022)
Background: Several automated computed tomography perfusion software applications have been developed to provide support in the definition of ischemic core and penumbra in acute ischemic stroke. However, the degree of interchangeability between software packages is not yet clear. Our study aimed to evaluate 2 commonly used automated perfusion software applications (Syngo.via and RAPID) for the indication of ischemic core with respect to the follow-up infarct volume (FIV) after successful recanalization and with consideration of the clinical impact. Methods: Retrospectively, 154 patients with large vessel occlusion of the middle cerebral artery or the internal carotid artery, who underwent endovascular therapy with a consequent Thrombolysis in Cerebral Infarction 3 result within 2 hours after computed tomography perfusion, were included. Computed tomography perfusion core volumes were assessed with both software applications with different thresholds for relative cerebral blood flow (rCBF). The results were compared with the FIV on computed tomography within 24 to 36 hours after recanalization. Bland-Altman was applied to display the levels of agreement and to evaluate systematic differences. Results: Highest correlation between ischemic core volume and FIV without significant differences was found at a threshold of rCBF<38% for the RAPID software (r=0.89, P<0.001) and rCBF<25% for the Syngo software (r=0.87, P<0.001). Bland-Altman analysis revealed best agreement in these settings. In the vendor default settings (rCBF<30% for RAPID and rCBF<20% for Syngo) correlation between ischemic core volume and FIV was also high (RAPID: r=0.88, Syngo: r=0.86, P<0.001), but mean differences were significant (P<0.001). The risk of critical overestimation of the FIV was higher with rCBF<38% (RAPID) and rCBF<25% (Syngo) than in the default settings. Conclusions: By adjusting the rCBF thresholds, comparable results with reliable information on the FIV after complete recanalization can be obtained both with the RAPID and Syngo software. Keeping the software specific default settings means being more inclusive in patient selection, but forgo the highest possible accuracy in the estimation of the FIV.
CRIS-Team WoS Importer:2022-05-13

Compromised cardiovascular autonomic modulation in patient with acute ischemic stroke improves after three & six months - Wang, Ruihao; Macha, Kosmas; Köhn, Julia; Köhn, Julia; Siedler, Gabriela; Winder, Klemens; Gerner, Stefan; Schwab, Stefan; Koehrmann, M.; Kallmünzer, Bernd; Hilz, Max-Josef (EUROPEAN JOURNAL OF NEUROLOGY, 2021)
CRIS-Team WoS Importer:2021-07-23

Cooling in intracerebral hemorrhage (CINCH) trial: Protocol of a randomized German-Austrian clinical trial - Kollmar, Rainer; Juettler, Eric; Huttner, Hagen; Dörfler, Arnd; Staykov, Dimitre; Kallmünzer, Bernd; Schmutzhard, Erich; Schwab, Stefan; Broessner, Gregor (International Journal of Stroke, 2012)
Background: Intracerebral hemorrhage accounts for up to 15% of all strokes and is frequently associated with poor functional outcome and high mortality. So far, there is no clear evidence for a specific therapy, apart from general stroke unit or neurointensive care and management of secondary complications. Promising experimental and pilot clinical data support the use of therapeutic hypothermia after intracerebral hemorrhage. Aims: The study aims to determine if therapeutic hypothermia improves survival rates and reduces cerebral lesion volume after large intracerebral hemorrhage compared with conventional treatment. Material and methods: The Cooling in IntraCerebral Hemorrhage trial is a prospective, multicenter, interventional, randomized, parallel, two-arm (1:1) phase II trial with blinded end-point adjudication. Enrolment: 50 patients (age: 18 to 65 years) with large (25 to 64ml on cranial computertomography), primary intracerebral hemorrhage of the basal ganglia or thalamus within 6 to 18h after symptom onset are randomly allocated to therapeutic hypothermia for eight-days or conventional temperature management. In the therapeutic hypothermia group, a target temperature of 35·0°C is achieved by endovascular catheters and followed by slow controlled rewarming. Data analysis is based on the intent-to-treat population. The primary outcome measure of the study is the development in total lesion volume on cranial computertomography (intracerebral hemorrhage plus perihemorrhagic edema on day 8±0·5 and day 11±0·5 after intracerebral hemorrhage) and the mortality after 30 days. Secondary end-points are the in-hospital mortality, mortality, and functional outcome (modified Rankin Scale and Barthel-Index) after 90 and 180 days. Safety measures include any adverse events associated with therapeutic hypothermia. Discussion: In the face of a lack of evidence-based therapies for patients with large intracerebral hemorrhage, new promising approaches are desperately needed, but need evaluation in randomized controlled trials. Conclusion: The results of Cooling in IntraCerebral Hemorrhage trial are believed to directly influence future therapy of large intracerebral hemorrhage. © 2012 The Authors. International Journal of Stroke © 2012 World Stroke Organization.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Edema; Hypothermia; Intracerebral hemorrhage; Neuroprotection; Stroke

Correction to: Neck cooling induces blood pressure increase and peripheral vasoconstriction in healthy persons (Neurological Sciences, (2020), 41, 9, (2521-2529), 10.1007/s10072-020-04349-x) - Köhn, Julia; Wang, Ruihao; de Rojas Leal, Carmen; Kallmünzer, Bernd; Winder, Klemens; Köhrmann, Martin; Kollmar, Rainer; Schwab, Stefan; Hilz, Max-Josef (Neurological Sciences, 2021)
The article “Neck cooling induces blood pressure increase and peripheral vasoconstriction in healthy persons”, written by Julia Koehn, Ruihao Wang, Carmen de Rojas Leal, Bernd Kallmünzer, Klemens Winder, Martin Köhrmann, Rainer Kollmar, Stefan Schwab and Max J. Hilz, was originally published Online First without Open Access. After publication in volume 41, issue 9, page 2521–2529 the authors decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http:// creat iveco mmons. org/ licen ses/ by/4.0. The original article has been corrected.
CRIS-Team Scopus Importer:2021-07-16

Dabigatran for prevention of stroke after embolic stroke of undetermined source - Diener, Hans Christoph; Sacco, Ralph L.; Donald Easton, J.; Granger, Christopher B.; Bernstein, Richard A.; Uchiyama, Shinichiro; Kreuzer, Jörg; Cronin, Lisa; Cotton, Daniel; Grauer, Claudia; Brueckmann, Martina; Chernyatina, Marina; et al. (New England Journal of Medicine, 2019)
BACKGROUND Cryptogenic strokes constitute 20 to 30% of ischemic strokes, and most cryptogenic strokes are considered to be embolic and of undetermined source. An earlier randomized trial showed that rivaroxaban is no more effective than aspirin in preventing recurrent stroke after a presumed embolic stroke from an undetermined source. Whether dabigatran would be effective in preventing recurrent strokes after this type of stroke was unclear. METHODS We conducted a multicenter, randomized, double-blind trial of dabigatran at a dose of 150 mg or 110 mg twice daily as compared with aspirin at a dose of 100 mg once daily in patients who had had an embolic stroke of undetermined source. The primary outcome was recurrent stroke. The primary safety outcome was major bleeding. RESULTS A total of 5390 patients were enrolled at 564 sites and were randomly assigned to receive dabigatran (2695 patients) or aspirin (2695 patients). During a median follow-up of 19 months, recurrent strokes occurred in 177 patients (6.6%) in the dabigatran group (4.1% per year) and in 207 patients (7.7%) in the aspirin group (4.8% per year) (hazard ratio, 0.85; 95% confidence interval [CI], 0.69 to 1.03; P=0.10). Ischemic strokes occurred in 172 patients (4.0% per year) and 203 patients (4.7% per year), respectively (hazard ratio, 0.84; 95% CI, 0.68 to 1.03). Major bleeding occurred in 77 patients (1.7% per year) in the dabigatran group and in 64 patients (1.4% per year) in the aspirin group (hazard ratio, 1.19; 95% CI, 0.85 to 1.66). Clinically relevant nonmajor bleeding occurred in 70 patients (1.6% per year) and 41 patients (0.9% per year), respectively. CONCLUSIONS In patients with a recent history of embolic stroke of undetermined source, dabigatran was not superior to aspirin in preventing recurrent stroke. The incidence of major bleeding was not greater in the dabigatran group than in the aspirin group, but there were more clinically relevant nonmajor bleeding events in the dabigatran group.
CRIS-Team Scopus Importer:2019-05-28

Dabigatran Plasma Levels in Acute Cerebrovascular Events - Volbers, Bastian; Köhrmann, Martin; Kallmünzer, Bernd; Kurka, Natalia; Breuer, Lorenz; Ringwald, Juergen; Schwab, Stefan (Journal of Stroke and Cerebrovascular Diseases, 2016)
Oral anticoagulation with dabigatran was shown to be effective for stroke prevention in patients with nonvalvular atrial fibrillation without the need for laboratory monitoring. However, a recent publication based on data of the Randomized Evaluation of Long-Term Anticoagulation Therapy study reported that ischemic stroke and bleeding outcomes are correlated with dabigatran plasma concentration (DPC). DPC was determined at a prespecified time point and correlated with cardiovascular events at any time during follow-up. Because of the known variability of DPC, among others depending on renal function, this approach might compromise data evaluation. We report on dabigatran plasma levels in acute cerebrovascular events.Consecutive patients with acute ischemic stroke (AIS) or intracerebral hemorrhage (ICH) while taking dabigatran were retrospectively identified if admission DPC was available. DPC was determined using the diluted thrombin time (Hemoclot (HYPHEN BioMed, Neuville sur Oise, France)). Creatinine clearance (CrCl) was determined by measuring creatinine in plasma and 24-hour urine.Fifteen AIS and 4 ICH patients were included. Median DPC on admission was significantly higher in ICH patients than in AIS patients (135 ng/mL [interquartile range IQR 79-218] and 69.1 ng/mL [IQR 20.6-85.0], respectively; P = .035). Increased CrCl (values above published normal range) was correlated with lower median DPC (60 ng/mL [IQR 10-69] versus 100 ng/mL [IQR 79-157] in patients with normal CrCl, P = .01).Higher DPC was found in ICH patients than in AIS patients in temporal proximity to the event. Both decreased and increased renal functions seem to have an important influence on DPC.
EVALuna2:15996

Decompressive craniectomy plus best medical treatment versus best medical treatment alone for spontaneous severe deep supratentorial intracerebral haemorrhage: a randomised controlled clinical trial - Beck, Jürgen; Fung, Christian; Strbian, Daniel; Bütikofer, Lukas; Z'Graggen, Werner J.; Lang, Matthias F.; Beyeler, Seraina; Gralla, Jan; Ringel, Florian; Schaller, Karl; Plesnila, Nikolaus; Arnold, Marcel; et al. (Lancet, 2024)
Background: It is unknown whether decompressive craniectomy improves clinical outcome for people with spontaneous severe deep intracerebral haemorrhage. The SWITCH trial aimed to assess whether decompressive craniectomy plus best medical treatment in these patients improves outcome at 6 months compared to best medical treatment alone. Methods: In this multicentre, randomised, open-label, assessor-blinded trial conducted in 42 stroke centres in Austria, Belgium, Finland, France, Germany, the Netherlands, Spain, Sweden, and Switzerland, adults (18–75 years) with a severe intracerebral haemorrhage involving the basal ganglia or thalamus were randomly assigned to receive either decompressive craniectomy plus best medical treatment or best medical treatment alone. The primary outcome was a score of 5–6 on the modified Rankin Scale (mRS) at 180 days, analysed in the intention-to-treat population. This trial is registered with ClincalTrials.gov, NCT02258919, and is completed. Findings: SWITCH had to be stopped early due to lack of funding. Between Oct 6, 2014, and April 4, 2023, 201 individuals were randomly assigned and 197 gave delayed informed consent (96 decompressive craniectomy plus best medical treatment, 101 best medical treatment). 63 (32%) were women and 134 (68%) men, the median age was 61 years (IQR 51–68), and the median haematoma volume 57 mL (IQR 44–74). 42 (44%) of 95 participants assigned to decompressive craniectomy plus best medical treatment and 55 (58%) assigned to best medical treatment alone had an mRS of 5–6 at 180 days (adjusted risk ratio [aRR] 0·77, 95% CI 0·59 to 1·01, adjusted risk difference [aRD] −13%, 95% CI −26 to 0, p=0·057). In the per-protocol analysis, 36 (47%) of 77 participants in the decompressive craniectomy plus best medical treatment group and 44 (60%) of 73 in the best medical treatment alone group had an mRS of 5–6 (aRR 0·76, 95% CI 0·58 to 1·00, aRD −15%, 95% CI −28 to 0). Severe adverse events occurred in 42 (41%) of 103 participants receiving decompressive craniectomy plus best medical treatment and 41 (44%) of 94 receiving best medical treatment. Interpretation: SWITCH provides weak evidence that decompressive craniectomy plus best medical treatment might be superior to best medical treatment alone in people with severe deep intracerebral haemorrhage. The results do not apply to intracerebral haemorrhage in other locations, and survival is associated with severe disability in both groups. Funding: Swiss National Science Foundation, Swiss Heart Foundation, Inselspital Stiftung, and Boehringer Ingelheim.
CRIS-Team Scopus Importer:2024-06-07

Demyelinating disease and anti-N-methyl-D-aspartate receptor immunoglobulin G antibodies: a case report - Waschbisch, Anne; Kallmünzer, Bernd; Schwab, Stefan; Gölitz, Philipp; Vincent, Angela; Lee, De Hyung; Linker, Ralf (BMC Research Notes, 2014)
Anti-N-methyl-D-aspartate receptor immunoglobulin G antibodies directed against the GluN1 subunit are considered highly specific for anti-N-methyl-D-aspartate receptor encephalitis, a severe clinical syndrome characterized by seizures, psychiatric symptoms, orofacial dyskinesia and autonomic dysfunction.Here we report a 33 year old Caucasian male patient with clinically definite multiple sclerosis who was found to be positive for anti-N-methyl-D-aspartate receptor antibodies. Rituximab therapy was initiated. On the 18 months follow-up visit the patient was found to be clinically stable, without typical signs of anti-N-methyl-D-aspartate receptor encephalitis.Our findings add to the growing evidence for a possible association between anti-N-methyl-D-aspartate receptor encephalitis and demyelinating diseases.
EVALuna2:22345

Diagnostik Lumbar Puncture - Step by Step - Siedler, Gabriela; Kallmünzer, Bernd; Schwab, Stefan (Deutsche Medizinische Wochenschrift, 2019)
Performing a diagnostic lumbar puncture is an essential clinical skill for the clinician. The procedure is of high importance for both, the emergency care for patients with suspected infection of the cerebral nervous system or subarachnoidal hemorrhage, as well as the elective diagnostic work up of chronic disease including multiple sclerosis and dementia. Furthermore the technique's principles are applied for spinal anesthesia or the intrathecal administration of drugs. This article describes a Standard Operating Procedure for the lumbar puncture step by step. Based on the latest evidence, it particularly focusses on clinically relevant questions and practical aspects.
EVALuna2:204469

Direct Oral Anticoagulant Plasma Levels for the Management of Acute Ischemic Stroke - Marsch, Armin; Macha, Kosmas; Siedler, Gabriela; Breuer, Lorenz; Strasser, Erwin; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Cerebrovascular Diseases, 2019)
Introduction: The management of acute ischemic stroke in patients on direct oral anticoagulants (DOACs) is challenging. However, the substance-specific plasma level could guide treatment decisions on recanalization therapies. We present a plasma-level-based protocol for emergency treatment of stroke patients on oral anticoagulants. Bleeding complications and clinical outcome for patients on DOACs are reported and compared to patients on vitamin K antagonists (VKAs). Methods: In patients with acute ischemic stroke and suspected use of DOACs within 48 h prior to hospital admission, plasma levels were measured using the calibrated Xa-activity (apixaban, edoxaban, rivaroxaban) or the Hemoclot®-assay (dabigatran). Levels <50 ng/mL were supportive for thrombolysis, while high values >100 ng/mL excluded patients from recombinant tissue plasminogen activator use. For patients on VKAs, the cutoff was set at international normalized ratio of 1.7. Endovascular thrombectomy of a large vessel occlusion was performed independently from coagulation testing. Consecutive patients were included in an observational registry. Results: Five hundred and twenty-two patients (261 on VKAs and 261 on DOACs) were included. Thirty patients (11.5%) on VKAs and 24 (9.2%) on DOACs received thrombolysis, followed by mechanical thrombectomy in 10 and 14 patients, respectively. Seventeen patients in each group received thrombectomy only. Symptomatic intracranial hemorrhage associated with thrombolysis occurred in 1 patient on VKA (3.3%) and 1 on DOAC (4.2%; p = 0.872). The turnaround time of specific assays did not show a significant delay in comparison to standard coagulation parameters. Conclusion: DOAC plasma levels could support decisions on emergency treatment of ischemic stroke. Systemic thrombolysis below suggested thresholds appears preliminary feasible and safe without an excess in bleeding complications.
CRIS-Team Scopus Importer:2019-09-24

Direct oral anticoagulants versus Vitamin K antagonists after a recent ischemic stroke or TIA- a pooled individual patient data analysis - Seiffge, David; Paciaroni, Maurizio; Wilson, Duncan; Koga, Masatoshi; Macha, Kosmas; Cappellari, Manuel; Schaedelin, Sabine; Shakeshaft, Clare; Takagi, Masahito; Tsivgoulis, Georgios; Bonetti, Bruno; Kallmünzer, Bernd; et al. (NEUROLOGY, 2019)
CRIS-Team WoS Importer:2019-08-02

Direct oral anticoagulants versus vitamin K antagonists after recent ischemic stroke in patients with atrial fibrillation - Seiffge, David J.; Paciaroni, Maurizio; Wilson, Duncan; Koga, Masatoshi; Macha, Kosmas; Cappellari, Manuel; Schaedelin, Sabine; Shakeshaft, Clare; Takagi, Masahito; Tsivgoulis, Georgios; Bonetti, Bruno; Kallmünzer, Bernd; et al. (Annals of Neurology, 2019)
Objective: We compared outcomes after treatment with direct oral anticoagulants (DOACs) and vitamin K antagonists (VKAs) in patients with atrial fibrillation (AF) and a recent cerebral ischemia. Methods: We conducted an individual patient data analysis of seven prospective cohort studies. We included patients with AF and a recent cerebral ischemia (<3 months before starting oral anticoagulation) and a minimum follow-up of 3 months. We analyzed the association between type of anticoagulation (DOAC versus VKA) with the composite primary endpoint (recurrent ischemic stroke [AIS], intracerebral hemorrhage [ICH], or mortality) using mixed-effects Cox proportional hazards regression models; we calculated adjusted hazard ratios (HRs) with 95% confidence intervals (95% CIs). Results: We included 4,912 patients (median age, 78 years [interquartile range IQR, 71–84]; 2,331 [47.5%] women; median National Institute of Health Stroke Severity Scale at onset, 5 [IQR, 2–12]); 2,256 (45.9%) patients received VKAs and 2,656 (54.1%) DOACs. Median time from index event to starting oral anticoagulation was 5 days (IQR, 2–14) for VKAs and 5 days (IQR, 2–11) for DOACs (p = 0.53). There were 262 acute ischemic strokes (AISs; 4.4%/year), 71 intracranial hemorrrhages (ICHs; 1.2%/year), and 439 deaths (7.4%/year) during the total follow-up of 5,970 patient-years. Compared to VKAs, DOAC treatment was associated with reduced risks of the composite endpoint (HR, 0.82; 95% CI, 0.67–1.00; p = 0.05) and ICH (HR, 0.42; 95% CI, 0.24–0.71; p < 0.01); we found no differences for the risk of recurrent AIS (HR, 0.91; 95% CI, 0.70–1.19; p = 0.5) and mortality (HR, 0.83; 95% CI, 0.68–1.03; p = 0.09). Interpretation: DOAC treatment commenced early after recent cerebral ischemia related to AF was associated with reduced risk of poor clinical outcomes compared to VKA, mainly attributed to lower risks of ICH. ANN NEUROL 2019.
CRIS-Team Scopus Importer:2019-05-17

Early versus late start of direct oral anticoagulants after acute ischaemic stroke linked to atrial fibrillation: an observational study and individual patient data pooled analysis - De Marchis, Gian Marco; Seiffge, David J.; Schaedelin, Sabine; Wilson, Duncan; Caso, Valeria; Acciarresi, Monica; Tsivgoulis, Georgios; Koga, Masatoshi; Yoshimura, Sohei; Toyoda, Kazunori; Cappellari, Manuel; Bonetti, Bruno; et al. (Journal of Neurology Neurosurgery and Psychiatry, 2021)
Objective The optimal timing to start direct oral anticoagulants (DOACs) after an acute ischaemic stroke (AIS) related to atrial fibrillation (AF) remains unclear. We aimed to compare early (<= 5 days of AIS) versus late (>5 days of AIS) DOAC-start. Methods This is an individual patient data pooled analysis of eight prospective European and Japanese cohort studies. We included patients with AIS related to non-valvular AF where a DOAC was started within 30 days. Primary endpoints were 30-day rates of recurrent AIS and ICH. Results A total of 2550 patients were included. DOACs were started early in 1362 (53%) patients, late in 1188 (47%). During 212 patient-years, 37 patients had a recurrent AIS (1.5%), 16 (43%) before a DOAC was started; 6 patients (0.2%) had an ICH, all after DOAC-start. In the early DOAC-start group, 23 patients (1.7%) suffered from a recurrent AIS, while 2 patients (0.1%) had an ICH. In the late DOAC-start group, 14 patients (1.2%) suffered from a recurrent AIS; 4 patients (0.3%) suffered from ICH. In the propensity score-adjusted comparison of late versus early DOAC-start groups, there was no statistically significant difference in the hazard of recurrent AIS (aHR=1.2, 95% CI 0.5 to 2.9, p=0.69), ICH (aHR=6.0, 95% CI 0.6 to 56.3, p=0.12) or any stroke. Conclusions Our results do not corroborate concerns that an early DOAC-start might excessively increase the risk of ICH. The sevenfold higher risk of recurrent AIS than ICH suggests that an early DOAC-start might be reasonable, supporting enrolment into randomised trials comparing an early versus late DOAC-start.
CRIS-Team WoS Importer:2021-12-03

EARLY VERSUS LATE START OF DIRECT ORAL ANTICOAGULANTS AFTER AN ISCHEMIC STROKE LINKED TO ATRIAL FIBRILLATION - A MULTICENTER, PROPENSITY SCORE ADJUSTED ANALYSIS. - De Marchis, G. M.; Seiffge, D.; Schadelin, S.; Wilson, D.; Caso, V.; Acciarresi, M.; Tsivgoulis, G.; Koga, M.; Yoshimura, S.; Toyoda, K.; Cappellari, M.; Bonetti, B.; et al. (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Editorial: Pushing the boundaries in acute ischemic stroke treatment - Volbers, Bastian; Kallmünzer, Bernd; Seiffge, David J. (Frontiers in Neurology, 2023)
CRIS-Team Scopus Importer:2023-09-08
Keywords: acute ischemic stroke; cardiac myxoma; extended time window; intracerebral hemorrhage (ICH); mechanical thrombectomy; non-contrast computer tomography (NCCT); telestroke network; thrombolysis (for acute ischemic stroke)

Endovascular thrombectomy for ischemic stroke - Kallmünzer, Bernd; Koehrmann, M. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2017)
The standard of care for patients with acute stroke of the anterior circulation and large vessel occlusion is the combined treatment with intravenous rt-PA (recombinant tissue-type plasminogen activator) and endovascular thrombectomy. The therapy is highly effective while reducing functional deficits and long-term disability. International guidelines recommend thrombectomy during the first 6 h after symptom onset, but new evidence supports its use in selected patients within a time window of up to 24 h. Eligible patients show a clinical core mismatch, i. e. severe neurologic deficits contrasting to a small core of cerebral infarction. Future research questions regard the treatment of vessel occlusion at the M2 segments as well as the best anesthetic management during the intervention. The infrastructure of stroke care especially in rural areas is based on the drip-and-ship paradigm that implies emergency treatment with the start of intravenous thrombolysis at the nearest hospital followed by transport to an interventional center in case of large vessel occlusion.
EVALuna2:22559

Endovascular thrombectomy in patients with anterior circulation stroke: an emulated real-world comparison - Sembill, Jochen; Sprügel, Maximilian; Haupenthal, David; Kremer, Svenja; Knott, Michael; Mühlen, Iris; Kallmünzer, Bernd; Kuramatsu, Joji (Neurological Research and Practice, 2024)
Background: Endovascular thrombectomy (EVT) has been proven effective in anterior circulation stroke due to large vessel occlusion (LVO). However, translation from randomized clinical trials (RCTs) with highly selected patients to real-world requires confirmation, particularly to identify associations outside of strict selection criteria. Aims: This study aims to compare functional outcomes after EVT in real-world with those reported in RCTs, and to identify associations with functional outcome after EVT outside RCT-criteria. Methods: This study analyzed longitudinal German real-world data from the Stroke Research Consortium in Northern Bavaria (STAMINA) cohort from January, 2015 to June, 2019. We conducted a trial emulation, comparing patients with anterior circulation stroke and LVO meeting selection criteria for RCTs investigating EVT (1) predominantly within 6 hours with those from HERMES meta-analysis, and (2) within 6-24 hours with those from AURORA meta-analysis. We (3) analyzed treatment effects of EVT and association with functional outcome in patients treated outside RCT criteria. Results: Of 598 patients, 281 (47.0%) met RCT-criteria for treatment within 6 hours (hereinafter STAMINA-HERMES), 74 (12.4%) met RCT-criteria for treatment within 6–24 hours (STAMINA-AURORA), and 277 (46.3%) patients received EVT outside RCT-criteria. We observed no difference in rates of functional independence or mortality, comparing STAMINA-HERMES with HERMES meta-analysis (mRS 0-1: n=120/281 [43%] vs. 291/633 [46%], p=0.36; mortality: n=34/281 [12%] vs. 97/633 [15%], p=0.20), and STAMINA-AURORA with AURORA meta-analysis (mRS 0-1: n=26/74 [35%] vs. 122/266 [46%], p=0.10, mortality: n=10/74 [14%] vs. 45/266 [17%], p=0.48). Patients treated outside RCT-criteria had worse outcome (mRS 0-1: n=38/277 [14%], mortality: n=90/277 [32%], both p<0.001); possibly driven by pre-existing functional dependence (n=172/277 [62%]). Compared to matched controls, EVT outside of RCT-criteria was associated with lower mortality (absolute treatment effect: -14%, 95% Confidence Interval [CI] -23 to -5, p<0.01), but not with recovery to functional independence or premorbid functional status (treatment effect: 4%, CI -4 to 11, p=0.34), which was associated with lower NIHSS (Odds ratio [OR] 0.86, CI 0.80-0.92, p<0.001) and age (OR 0.95, CI 0.93-0.98, p=0.002). Conclusions: Translation of EVT outcomes reported in RCTs into real-world is possible, however, almost half of patients did not meet trial criteria. Identification of patients who functionally benefit from frequently performed EVT outside RCT-criteria requires further investigation. Trial registration: Clinicaltrials.gov, NCT04357899.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Stroke; Thrombectomy; Treatment

Endovascular treatment in patients with large vessel occlusion: reduced mortality despite minimal penumbra - Schmidt, Manuel; Breuer, Lorenz; Kallmünzer, Bernd; Schwab, Stefan; Dörfler, Arnd; Engelhorn, Tobias; Hölter, Philip (Neuroradiology, 2019)
Purpose: In patients with acute ischemic stroke (AIS) caused by large vessel occlusion (LVO), endovascular treatment (EVT) is highly effective for emergency revascularization. However, data on functional outcome are lacking for patients, which show no or minimal mismatch between ischemic core and penumbra. Methods: Forty-five patients with AIS due to LVO of the anterior circulation were retrospectively analyzed within 6 h since onset when administered to our department. In all patients, there was no relevant penumbra according to CT perfusion (CTP). Functional outcome, defined by the modified Rankin Scale (mRS) at 30 and 90 days, was analyzed according to LVO treatment (EVT versus non-EVT). Confounding was addressed by multivariable regression analyses. Results: mRS values at 30 days (p = 0.002) and 90 days (p = 0.005) after AIS occurrence were significantly lower in patients who had received EVT. There was no significant difference regarding good functional outcome, as measured by mRS of 0–2 at 30 (p = 0.432) and 90 days, respectively (p = 0.186). Mortality was significantly reduced in patients undergoing EVT at 30-day (p < 0.001) and at 90-day follow-up (p = 0.003), respectively. Multivariable regression analyses revealed that EVT was associated with reduced mortality at 30 (OR 0.091; CI (0.013–0.612); p = 0.014) and 90 days (OR 0.134; CI (0.021–0.857); p = 0.034) after AIS. Conclusions: Despite a small and highly selected patient collective, our study indicates that AIS patients with minimal penumbra in CTP might benefit from EVT in terms of reduced mortality at 30 and 90 days after AIS. However, in this group of patients, we could not prove favorable functional outcome at 30 and 90 days, despite receiving EVT.
CRIS-Team Scopus Importer:2019-09-17
Keywords: CTP; Endovascular treatment; Mortality; Penumbra; Stroke

EUROHYP-1: EUROPEAN, MULTICENTRE, RANDOMISED, PHASE III CLINICAL TRIAL OF THERAPEUTIC HYPOTHERMIA PLUS BEST MEDICAL TREATMENT VS BEST MEDICAL TREATMENT ALONE FOR ACUTE ISCHAEMIC STROKE - Petersson, J.; Van Der Worp, H. B.; Macleod, M. R.; Kollmar, R.; Krieger, D. W.; Staykov, D.; Szabo, I.; Kallmünzer, Bernd; Schwab, Stefan (2018)
EVALuna2:36384

Extended Multimodal Flat Detector CT Imaging in Acute Ischemic Stroke: A Pilot Study - Hölter, Philip; Lang, Stefan; Beuscher, Vanessa; Kallmünzer, Bernd; Manhart, Michael; Schwab, Stefan; Dörfler, Arnd (Journal of Digital Imaging, 2023)
By using Flat detector computed tomography (FD-CT), a one-stop-shop approach in the diagnostic workup of acute ischemic stroke (AIS) might be achieved. Although information on upstream vessels is warranted, dedicated FD-CT protocols which include the imaging of the cervical vasculature are still lacking. We aimed to prospectively evaluate the implementation of a new multimodal FD-CT protocol including cervical vessel imaging in AIS patients. In total, 16 patients were included in this study. Eight patients with AIS due to large vessel occlusion (LVO) prospectively received a fully multimodal FD-CT imaging, including non-enhanced flat detector computed tomography (NE-FDCT), dynamic perfusion flat detector computed tomography (FD-CTP) and flat detector computed tomography angiography (FD-CTA) including cervical imaging. For comparison of time metrics and image quality, eight AIS patients, which received multimodal CT imaging, were included retrospectively. Although image quality of NE-FDCT and FD-CTA was rated slightly lower than NE-CT and CTA, all FD-CT datasets were of diagnostic quality. Intracerebral hemorrhage exclusion and LVO detection was reliably possible. Median door-to-image time was comparable for the FD-CT group and the control group (CT:30 min, IQR27-58; FD-CT:44.5 min, IQR31-55, p = 0.491). Door-to-groin-puncture time (CT:79.5 min, IQR65-90; FD-CT:59.5 min, IQR51-67; p = 0.016) and image-to-groin-puncture time (CT:44 min, IQR30-50; FD-CT:14 min, IQR12-18; p < 0.001) were significantly shorter, when patients were directly transferred to the angiosuite, where FD-CT took place. Our study indicates that using a new fully multimodal FD-CT approach including imaging of cervical vessels for first-line imaging in AIS patients is feasible and comparable to multimodal CT imaging with substantial potential to streamline the stroke workflow.
CRIS-Team Scopus Importer:2023-02-03
Keywords: Flat Detector Computed Tomography; Interventional; Stroke; Workflow

Fatal intracranial haemorrhage occurring after oral anticoagulant treatment initiation for secondary stroke prevention in patients with atrial fibrillation - Tsivgoulis, G.; Katsanos, A. H.; Seiffge, D. J.; Paciaroni, M.; Wilson, D.; Koga, M.; Macha, Kosmas; Cappellari, M.; Kallmünzer, Bernd; Polymeris, A. A.; Toyoda, K.; Caso, V.; et al. (European Journal of Neurology, 2020)
Background and purpose: In this pooled analysis of seven multicentre cohorts potential differences were investigated in the incidence, characteristics and outcomes between intracranial haemorrhages (ICHs) associated with the use of non-vitamin K antagonist oral anticoagulants (NOAC-ICH) or with vitamin K antagonists (VKA-ICH) in ischaemic stroke patients after oral anticoagulant treatment initiation for atrial fibrillation (AF). Methods: Data from 4912 eligible AF patients who were admitted in a stroke unit with ischaemic stroke or transient ischaemic attack and who were treated with either VKAs or NOACs within 3 months post-stroke were included. Fatal ICH was defined as death occurring during the first 30 days after ICH onset. A meta-analysis of available observational studies reporting 30-day mortality rates from NOAC-ICH or VKA-ICH onset was additionally performed. Results: During 5970 patient-years of follow-up 71 participants had an ICH, of whom 20 were NOAC-ICH and 51 VKA-ICH. Patients in the two groups had comparable baseline characteristics, except for the higher prevalence of kidney disease in VKA-ICH patients. There was a non-significant higher number of fatal ICH in patients with VKAs (11 events per 3385 patient-years) than in those with NOACs (three events per 2623 patient-years; hazard ratio 0.32, 95% confidence interval 0.09–1.14). Three-month functional outcomes were similar (P > 0.2) in the two groups. The meta-analysis showed a lower 30-day mortality risk for patients with NOAC-ICH compared to VKA-ICH (relative risk 0.70, 95% confidence interval 0.51–0.95). Conclusions: Non-vitamin K oral anticoagulants for intracranial haemorrhages and VKA-ICH occurring during secondary stroke prevention of AF patients have comparable baseline characteristics and outcomes except for the risk of fatal ICH within 30 days, which might be greater in VKA-ICH.
CRIS-Team Scopus Importer:2020-05-22
Keywords: anticoagulation; cerebral haemorrhage; cerebral infarction; cerebrovascular diseases and cerebral circulation; neurological disorders

Functional Outcome of Intravenous Thrombolysis in Patients With Lacunar Infarcts in the WAKE-UP Trial - Barow, Ewgenia; Boutitie, Florent; Cheng, Bastian; Cho, Tae-Hee; Ebinger, Martin; Endres, Matthias; Fiebach, Jochen B.; Fiehler, Jens; Ford, Ian; Galinovic, Ivana; Nickel, Alina; Puig, Josep; et al. (JAMA Neurology, 2019)
IMPORTANCE The rationale for intravenous thrombolysis in patients with lacunar infarcts is debated, since it is hypothesized that the microvascular occlusion underlying lacunar infarcts might not be susceptible to pharmacological reperfusion treatment.
CRIS-Team WoS Importer:2019-07-26

Heart Failure in Ischemic Stroke: Relevance for Acute Care and Outcome - Siedler, Gabriela; Sommer, Kim; Macha, Kosmas; Marsch, Armin; Breuer, Lorenz; Stoll, Svenja; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd; Arnold, Martin (Stroke, 2019)
Background and Purpose- Heart failure (HF) in patients with acute ischemic stroke constitutes the source of various detrimental pathophysiologic mechanisms including prothrombotic and proinflammatory states, worsening of cerebral tissue oxygenation, and hemodynamic impairment. In addition, HF might affect the safety and efficacy of the acute recanalization stroke therapies. Methods- Patients treated with intravenous recombinant tissue-type plasminogen activator or mechanical recanalization at a universitary stroke center were included into a prospective registry. Patients received cardiological evaluation, including echocardiography, during acute care. Functional outcome was assessed after 90 days by structured telephone interviews. Safety and efficacy of intravenous thrombolysis and mechanical thrombectomy were investigated among patients with HF and compared with patients with normal cardiac function after propensity score matching. Results- One thousand two hundred nine patients were included. HF was present in 378 patients (31%) and an independent predictor of unfavorable functional outcome. Recanalization rates were equal among patients with HF after intravenous thrombolysis and after mechanical recanalization or combined treatment. The rate of secondary intracranial hemorrhage was not different (7% versus 8%; P=0.909 after thrombolysis and 15% versus 20%, P=0.364 after mechanical recanalization or combined therapy). Early mortality within 48 hours after admission was equal (<1.5% in both groups). Conclusions- In this real-world cohort of patients with stroke, HF was an independent predictor of unfavorable functional long-term outcome, while the safety and efficacy of intravenous thrombolysis and mechanical recanalization appeared unaffected.
EVALuna2:204477

Impact of heart rate dynamics on mortality in the early phase after ischemic stroke: a prospective observational trial - Kallmünzer, Bernd; Bobinger, Tobias; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Journal of Stroke and Cerebrovascular Diseases, 2015)
Growing evidence suggests that the heart rate (HR) at rest is an independent predictor of cardiovascular mortality. In ischemic stroke, continuous monitoring of HR is the standard of care, but systematic data on its dynamics and prognostic value during the acute phase are limited.In this prospective observational study, HR was measured by continuous electrocardiographic monitoring on admission and during the first 72 hours of care among patients who were awake with ischemic stroke and survived until discharge. Functional outcome was assessed after 90 days.Data from 702 consecutive patients were analyzed (median age, 73 years, 54% men). The time course of HR was initially characterized by a rapid decline during the first 12 hours after admission. Among patients who survived until day 90, this was followed by a continuous downward trend in HR, whereas death after discharge was associated with a secondary increase and a reversal point 12 hours after admission. After adjustment for established risk factors, this secondary increase during the acute period was an independent predictor of death (hazard ratio, 3.73; 95% confidence interval, 1.47-9.43; P = .005).A secondary rise of HR during care for acute ischemic stroke is an early sign of fatality and may represent a surrogate for an unfavorable sympathetic disinhibition. Further research is warranted to clarify the role of targeted HR reduction after ischemic stroke (http://clinicaltrials.gov/, unique identifier NCT01858779).
EVALuna2:12023

Impact of Vaccination Status on Outcome of Patients With COVID-19 and Acute Ischemic Stroke Undergoing Mechanical Thrombectomy - Deuschl, Cornelius; Goertz, Lukas; Kabbasch, Christoph; Köhrmann, Martin; Kleinschnitz, Christoph; Berlis, Ansgar; Maurer, Christoph Johannes; Mühlen, Iris; Kallmünzer, Bernd; Gawlitza, Matthias; Kaiser, Daniel P.O.; Klisch, Joachim; et al. (Journal of the American Heart Association, 2024)
BACKGROUND: Data on impact of COVID-19 vaccination and outcomes of patients with COVID-19 and acute ischemic stroke undergoing mechanical thrombectomy are scarce. Addressing this subject, we report our multicenter experience. METHODS AND RESULTS: This was a retrospective analysis of patients with COVID-19 and known vaccination status treated with mechanical thrombectomy for acute ischemic stroke at 20 tertiary care centers between January 2020 and January 2023. Baseline demographics, angiographic outcome, and clinical outcome evaluated by the modified Rankin Scale score at discharge were noted. A multivariate analysis was conducted to test whether these variables were associated with an unfavorable outcome, defined as modified Rankin Scale score >3. A total of 137 patients with acute ischemic stroke (48 vaccinated and 89 unvaccinated) with acute or subsided COVID-19 infection who underwent mechanical thrombectomy attributable to vessel occlusion were included in the study. Angiographic outcomes between vaccinated and unvaccinated patients were similar (modified Thrombolysis in Cerebral Infarction ≥2b: 85.4% in vaccinated patients versus 86.5% in unvaccinated patients; P=0.859). The rate of functional independence (modified Rankin Scale score, ≤2) was 23.3% in the vaccinated group and 20.9% in the unvaccinated group (P=0.763). The mortality rate was 30% in both groups. In the multivariable analysis, vaccination status was not a significant predictor for an unfavorable outcome (P=0.957). However, acute COVID-19 infection remained significant (odds ratio, 1.197 [95% CI, 1.007-1.417]; P=0.041). CONCLUSIONS: Our study demonstrated no impact of COVID-19 vaccination on angiographic or clinical outcome of COVID-19-positive patients with acute ischemic stroke undergoing mechanical thrombectomy, whereas worsening attributable to COVID-19 was confirmed.
CRIS-Team Scopus Importer:2024-05-17
Keywords: acute ischemic stroke; COVID‐19; COVID‐19 vaccination; mechanical thrombectomy

Improvement and stabilization of cardiovascular autonomic modulation three months after acute ischemic stroke - Wang, Ruihao; Macha, Kosmas; Köhn, Julia; Marsch, Armin; Winder, K.; Gerner, Stefan; Koehrmann, M.; Schwab, Stefan; Kallmünzer, Bernd; Hilz, Max-Josef (EUROPEAN JOURNAL OF NEUROLOGY, 2020)
CRIS-Team WoS Importer:2020-06-16

Influence of antithrombotic pre-treatment and time window on hemorrhagic complications of ivt in ischemic stroke - Macha, Kosmas; Hölter, Philip; Sembill, Jochen; Hock, Stefan; Siedler, Gabriela; Mühlen, Iris; Haupenthal, David; Schwab, Stefan; Kallmünzer, Bernd; Dörfler, Arnd (EUROPEAN JOURNAL OF NEUROLOGY, 2022)
CRIS-Team WoS Importer:2022-07-22

Influence of bundled care treatment on functional outcome in patients with intracerebral hemorrhage - Mrochen, Anne; Song, Yu; Harders, Verena; Sembill, Jochen; Sprügel, Maximilian; Hock, Stefan; Lang, Stefan; Engelhorn, Tobias; Kallmünzer, Bernd; Volbers, Bastian; Kuramatsu, Joji (Frontiers in Neurology, 2024)
Background and aims: General guideline recommendations in patients with intracerebral hemorrhage (ICH) include blood pressure-, temperature- and glucose management. The therapeutic effect of such a “care bundle” (blood pressure lowering, glycemic control, and treatment of pyrexia) on clinical outcomes becomes increasingly established. For the present study, we aimed to investigate associations of strict bundled care treatment (BCT) with clinical outcomes and characterize associations with key outcome effectors such as hematoma enlargement (HE) and peak perihemorrhagic edema (PHE). Methods: We screened consecutive ICH patients (n = 1,322) from the prospective UKER-ICH cohort study. BCT was defined as achieving and maintaining therapeutic ranges for systolic blood pressure (110–160 mmHg), glucose (80–180 mg/dL), and body temperature (35.5–37.5°C) over the first 72 h. The primary outcome was the functional outcome at 12 months (modified Rankin Scale (mRS) 0–3). Secondary outcomes included mortality at 12 months, the occurrence of hematoma enlargement, and the development of peak perihemorrhagic edema. Confounding was addressed by a doubly robust methodology to calculate the absolute treatment effect (ATE) and by calculating e-values. Results: A total of 681 patients remained for analysis, and 182 patients fulfilled all three BCT criteria and were compared to 499 controls. The ATE of BCT to achieve the primary outcome was 9.3%, 95% CI (1.7 to 16.9), p < 0.001; e-value: 3.1, CI (1.8). Mortality at 12 months was significantly reduced by BCT [ATE: −12.8%, 95% CI (−19.8 to −5.7), p < 0.001; e-value: 3.8, CI (2.2)], and no association was observed for HE or peak PHE. Significant drivers of BCT effect on the primary outcome were systolic blood pressure control (ATE: 15.9%) and maintenance of normothermia (ATE: 10.9%). Conclusion: Strict adherence to this “care bundle” over the first 72 h during acute hospital care in patients with ICH was independently associated with improved functional long-term outcome, driven by systolic blood pressure control and maintenance of normothermia. Our findings strongly warrant prospective validation to determine the generalizability especially in Western countries. Clinical trial registration:ClinicalTrials.gov, identifier [ID: NCT03183167].
CRIS-Team Scopus Importer:2024-08-30
Keywords: bundle; HE; ICH; PHE; treatment

Intensive heart rhythm monitoring to decrease ischemic stroke and systemic embolism—the Find-AF 2 study—rationale and design - Uhe, Tobias; Wasser, Katrin; Weber-Krüger, Mark; Schäbitz, Wolf Rüdiger; Köhrmann, Martin; Brachmann, Johannes; Laufs, Ulrich; Dichgans, Martin; Gelbrich, Götz; Petroff, David; Prettin, Christiane; Michalski, Dominik; et al. (American Heart Journal, 2023)
Background: Atrial fibrillation (AF) is one of the most frequent causes of stroke. Several randomized trials have shown that prolonged monitoring increases the detection of AF, but the effect on reducing recurrent cardioembolism, ie, ischemic stroke and systemic embolism, remains unknown. We aim to evaluate whether a risk-adapted, intensified heart rhythm monitoring with consequent guideline conform treatment, which implies initiation of oral anticoagulation (OAC), leads to a reduction of recurrent cardioembolism. Methods: Find-AF 2 is a randomized, controlled, open-label parallel multicenter trial with blinded endpoint assessment. 5,200 patients ≥ 60 years of age with symptomatic ischemic stroke within the last 30 days and without known AF will be included at 52 study centers with a specialized stroke unit in Germany. Patients without AF in an additional 24-hour Holter ECG after the qualifying event will be randomized in a 1:1 fashion to either enhanced, prolonged and intensified ECG-monitoring (intervention arm) or standard of care monitoring (control arm). In the intervention arm, patients with a high risk of underlying AF will receive continuous rhythm monitoring using an implantable cardiac monitor (ICM) whereas those without high risk of underlying AF will receive repeated 7-day Holter ECGs. The duration of rhythm monitoring within the control arm is up to the discretion of the participating centers and is allowed for up to 7 days. Patients will be followed for at least 24 months. The primary efficacy endpoint is the time until recurrent ischemic stroke or systemic embolism occur. Conclusions: The Find-AF 2 trial aims to demonstrate that enhanced, prolonged and intensified rhythm monitoring results in a more effective prevention of recurrent ischemic stroke and systemic embolism compared to usual care.
CRIS-Team Scopus Importer:2023-08-11

Ischemic stroke and dose adjustment of oral Factor Xa inhibitors in patients with atrial fibrillation - Stoll, Svenja; Macha, Kosmas; Marsch, Armin; Gerner, Stefan; Siedler, Gabriela; Fröhlich, Kilian; Volbers, Bastian; Strasser, Erwin; Schwab, Stefan; Kallmünzer, Bernd (Journal of Neurology, 2020)
Background: Oral Factor Xa inhibitors for the prevention of stroke in atrial fibrillation require dose adjustment based on certain clinical criteria, but the off-label use of the reduced doses is common. Methods: Data from an observational registry including patients admitted with acute cerebral ischemia while taking oral Factor Xa inhibitors for atrial fibrillation between April 2016 and December 2018 were investigated. The dose regimen of the Xa inhibitor was classified as “appropriate”, “underdosed” and “overdosed” in conformity with the European Medicines Agency labelling. The effect of underdosing on the functional factor Xa plasma level on admission, the clinical stroke severity and the functional outcome after 3 months were investigated. Results: 254 patients with cerebral ischemia while on Factor Xa inhibitors were included. The dose regimen of the Factor Xa inhibitor was appropriate in 166 patients (65%), underdosed in 67 patients (26%) and overdosed in 21 patients (8%). Underdosing was associated with female sex, diabetes mellitus and higher CHA2DS2–Vasc scores. Underdosing independently predicted lower anti-Xa plasma levels on admission [median 69.4 ng/ml (IQR 0.0–121.6) vs. 129.2 ng/ml (65.5–207.2); p < 0.001], was associated with higher NIHSS scores on admission [median 5 (IQR 1–10) vs. 3 (1–7); p = 0.041] and worse functional outcome after 3 months (favorable outcome 26.9% vs. 46.9%; p = 0.025). Conclusion: One in three patients with ischemic stroke during treatment with oral Xa inhibitors used inappropriate dose regimens. Underdosing was associated with lower functional plasma levels, higher clinical stroke severity and worse functional outcome.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Atrial fibrillation; Direct oral anticoagulants; Dose reduction; Plasma levels; Stroke

Ischemic Stroke Despite Oral Anticoagulant Therapy in Patients With AF - What is the Risk of Recurrence and How to Prevent Further Events?. - Seiffge, David J.; De Marchis, Gian Marco; Koga, Masatoshi; Paciaroni, Maurizio; Cappellari, Manuel; Kallmünzer, Bernd; Macha, Kosmas; Wilson, Duncan; Engelter, Stefan; Werring, David J. (STROKE, 2019)
CRIS-Team WoS Importer:2019-08-23

Ischemic Stroke despite Oral Anticoagulant Therapy in Patients with Atrial Fibrillation - Seiffge, David J.; De Marchis, Gian Marco; Koga, Masatoshi; Paciaroni, Maurizio; Wilson, Duncan; Cappellari, Manuel; Macha, Kosmas; Tsivgoulis, Georgios; Ambler, Gareth; Arihiro, Shoji; Bonati, Leo H.; Bonetti, Bruno; et al. (Annals of neurology, 2020)
Objective: It is not known whether patients with atrial fibrillation (AF) with ischemic stroke despite oral anticoagulant therapy are at increased risk for further recurrent strokes or how ongoing secondary prevention should be managed. Methods: We conducted an individual patient data pooled analysis of 7 prospective cohort studies that recruited patients with AF and recent cerebral ischemia. We compared patients taking oral anticoagulants (vitamin K antagonists [VKA] or direct oral anticoagulants [DOAC]) prior to index event (OACprior) with those without prior oral anticoagulation (OACnaive). We further compared those who changed the type (ie, from VKA or DOAC, vice versa, or DOAC to DOAC) of anticoagulation (OACchanged) with those who continued the same anticoagulation as secondary prevention (OACunchanged). Time to recurrent acute ischemic stroke (AIS) was analyzed using multivariate competing risk Fine–Gray models to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: We included 5,413 patients (median age = 78 years [interquartile range (IQR) = 71–84 years]; 5,136 [96.7%] had ischemic stroke as the index event, median National Institutes of Health Stroke Scale on admission = 6 [IQR = 2–12]). The median CHA2DS2-Vasc score (congestive heart failure, hypertension, age≥ 75 years, diabetes mellitus, stroke/transient ischemic attack, vascular disease, age 65–74 years, sex category) was 5 (IQR = 4–6) and was similar for OACprior (n = 1,195) and OACnaive (n = 4,119, p = 0.103). During 6,128 patient-years of follow-up, 289 patients had AIS (4.7% per year, 95% CI = 4.2–5.3%). OACprior was associated with an increased risk of AIS (HR = 1.6, 95% CI = 1.2–2.3, p = 0.005). OACchanged (n = 307) was not associated with decreased risk of AIS (HR = 1.2, 95% CI = 0.7–2.1, p = 0.415) compared with OACunchanged (n = 585). Interpretation: Patients with AF who have an ischemic stroke despite previous oral anticoagulation are at a higher risk for recurrent ischemic stroke despite a CHA2DS2-Vasc score similar to those without prior oral anticoagulation. Better prevention strategies are needed for this high-risk patient group. ANN NEUROL 2020.
CRIS-Team Scopus Importer:2020-03-10

IV Thrombolysis for Acute Ischemic Stroke with Unknown Onset in Patients on Oral Anticoagulation - Macha, Kosmas; Sembill, Jochen; Mühlen, Iris; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Cerebrovascular Diseases, 2024)
Introduction: IV thrombolysis (IVT) is established in the unknown or extended time window based on multimodal imaging. Further, increasing evidence exists regarding IVT in patients on oral anticoagulation including direct oral anticoagulants (DOACs). However, data on IVT in ischemic stroke patients on oral anticoagulation with unknown time of stroke onset are sparse. Methods: This study bases on the longitudinal cohort study Stroke Research Consortium in Northern Bavaria (STAMINA; ClinicalTrials.gov Identifier: NCT04357899). Acute ischemic stroke patients treated with IVT in the unknown or extended time window from January 2015 to December 2019 were included. Patient selection was based on multimodal CT or MRI. Patients on oral anticoagulation (vitamin-K antagonist [VKA] or DOAC within 48 h) were eligible for IVT based on INR measurement (VKA) or plasma levels (DOAC) according to an institutional protocol. Primary outcomes were the incidence of any and symptomatic intracranial hemorrhage. Results: Of 170 ischemic stroke patients treated with IVT in the unknown or extended time window, 151 had no oral anticoagulation at stroke onset and 19 were on oral anticoagulation (6 on VKA and 13 on DOAC). The risk of symptomatic ICH according to ECASS II criteria was similar between the patients with and without oral anticoagulation (1 [5.3%] vs. 4 [2.7%], p = 0.453). After adjustment for confounding factors, pre-medication with oral anticoagulation was not associated with symptomatic ICH (aOR 1.02 [0.09-11.02], p = 0.988). Conclusion: IVT for ischemic stroke with unknown onset appeared safe in selected patients on oral anticoagulation with both DOAC and VKA.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Direct oral anticoagulant; Ischemic stroke; IV thrombolysis; Unknown onset; Vitamin-K antagonist

IV-Thrombolysis in Ischemic Stroke With Unknown Time of Onset—Safety and Outcomes in Posterior vs. Anterior Circulation Stroke - Macha, Kosmas; Hölter, Philip; Siedler, Gabriela; Wang, Ruihao; Knott, Michael; Stoll, Svenja; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Mühlen, Iris; Kallmünzer, Bernd (Frontiers in Neurology, 2021)
Background: rt-PA for ischemic stroke in the unknown or extended time window beyond the first 4. 5 h after symptom onset is safe and effective for certain patients after selection by multimodal neuroimaging. However, the evidence for this approach comes mainly from patients with anterior circulation stroke (ACS), while the data on posterior circulation stroke (PCS) are scarce. Methods: Ischemic stroke patients treated with IV-thrombolysis in the unknown or extended time window between January 2011 and May 2019 were identified from an institutional registry. The patients were categorized into PCS or ACS based on clinico-radiological findings. We analyzed the hemorrhagic complications, clinical and imaging efficacy outcomes, and mortality rates by comparing the PCS and ACS patient groups. Adjusted outcome analyses were performed after propensity score matching for the relevant factors. Results: Of the 182 patients included, 38 (20.9%) had PCS and 144 (79.1%) had ACS. Symptomatic acute large vessel occlusion (LVO) was present in 123 patients on admission [27 (22.0%) PCS and 96 (78.0%) ACS]. The score on the National Institutes of Health Stroke Scale (NIHSS), the time from last seen normal, and the door-to-needle times were similar in PCS and ACS. In patients with LVO, the NIHSS score was lower [8 (5–15) vs. 14 (9–18), p = 0.005], and infarction visible on follow-up imaging was less common [70.4 vs. 87.5%; aRD, −18.9% (−39.8 to −2.2%)] in the PCS patient group. There was a trend toward a lower risk for intracranial hemorrhage (ICH) following intravenous thrombolysis in PCS vs. ACS, without reaching a statistical significance [5.3 vs. 16.9%; aRD, −10.4% (−20.4 to 4.0%)]. The incidence of symptomatic ICH [according to the ECASS III criteria: 2.6 vs. 3.5%; aRD, −2.9% (−10.3 to 9.2%)], efficacy outcomes, and mortality rates were similar in PCS and ACS patients. Conclusions: In this real-world clinical cohort, the safety and the efficacy of rt-PA for ischemic stroke in the unknown or extended time window did not show relevant differences between PCS and ACS, with a trend toward less hemorrhagic complications in PCS. The findings reconfirm the clinician in the usage of rt-PA beyond the first 4.5 h also in selected patients with PCS.
CRIS-Team Scopus Importer:2021-10-01
Keywords: anterior circulation stroke; extended time window; IV-thrombolysis; posterior circulation stroke; wake-up stroke

Letter by Kallmünzer et al Regarding Article, "safety of Intravenous Thrombolysis among Patients Taking Direct Oral Anticoagulants: A Systematic Review and Meta-Analysis" - Kallmünzer, Bernd; Pott, Michael; Schwab, Stefan (Stroke, 2020)
CRIS-Team Scopus Importer:2020-07-17

Liquorpunktion – Schritt für Schritt - Siedler, Gabriela; Kallmünzer, Bernd; Schwab, Stefan (Deutsche Medizinische Wochenschrift, 2019)
Performing a diagnostic lumbar puncture is an essential clinical skill for the clinician. The procedure is of high importance for both, the emergency care for patients with suspected infection of the cerebral nervous system or subarachnoidal hemorrhage, as well as the elective diagnostic work up of chronic disease including multiple sclerosis and dementia. Furthermore the technique's principles are applied for spinal anesthesia or the intrathecal administration of drugs. This article describes a Standard Operating Procedure for the lumbar puncture step by step. Based on the latest evidence, it particularly focusses on clinically relevant questions and practical aspects.
CRIS-Team Scopus Importer:2019-10-08
Keywords: atraumatic needle; cerebrospinal fluid analysis; diagnostic lumbar puncture; post-lumbar; puncture headache

Long-Term Complications and Influence on Outcome in Patients Surviving Spontaneous Subarachnoid Hemorrhage - Gerner, Stefan; Reichl, Jonathan; Custal, Christina; Brandner, Sebastian; Eyüpoglu, Ilker Yasin; Lücking, Hannes; Hölter, Philip; Kallmünzer, Bernd; Huttner, Hagen (Cerebrovascular Diseases, 2020)
BACKGROUND: While the short-term clinical outcome of patients with subarachnoid hemorrhage (SAH) is well described, there are limited data on long-term complications and their impact on social reintegration. This study aimed to assess the frequency of complications post-SAH and to investigate whether these complications attribute to functional and self-reported outcomes as well as the ability to return to work in these patients. METHODS: This retrospective single-center study included patients with atraumatic SAH over a 5-year period at a tertiary care center. Patients received a clinical follow-up for 12 months. In addition to demographics, imaging data, and parameters of acute treatment, the rate and extent of long-term complications after SAH were recorded. The functional outcome was assessed using the modified Rankin Scale (mRS; favorable outcome defined as mRS = 0-2). Further outcomes comprised self-reported subjective health measured by the EQ-5D and return to work for SAH patients with appropriate age. Multivariable analyses including in-hospital parameters and long-term complications were conducted to identify parameters independently associated with outcomes in SAH survivors. RESULTS: This study cohort consisted of 505 SAH patients of whom 405 survived the follow-up period of 12 months (i.e., mortality rate of 19.8%). Outcome data were available in 359/405 (88.6%) patients surviving SAH. At 12 months, a favorable functional outcome was achieved in 287/359 (79.9%) and 145/251 (57.8%) SAH patients returned to work. The rates of post-acute complications were headache (32.3%), chronic hydrocephalus requiring permanent ventriculoperitoneal shunting (VP shunt 25.4%) and epileptic seizures (9.5%). Despite patient's and clinical characteristics, both presence of epilepsy and need for VP shunt were independently and negatively associated with a favorable functional outcome (epilepsy: adjusted odds ratio [aOR] (95% confidence interval [95% CI]): 0.125 [0.050-0.315]; VP shunt: 0.279 [0.132-0.588]; both p < 0.001) as well as with return to work (aOR [95% CI]: epilepsy 0.195 [0.065-0.584], p = 0.003; VP shunt 0.412 [0.188-0.903], p = 0.027). Multivariable analyses revealed presence of headache, VP shunt, or epilepsy to be significantly related to subjective health impairment (aOR [95% CI]: headache 0.248 [0.143-0.430]; epilepsy 0.223 [0.085-0.585]; VP shunt 0.434 [0.231-0.816]; all p < 0.01). CONCLUSIONS: Long-term complications occur frequently after SAH and are associated with an impairment of functional and social outcomes. Further studies are warranted to investigate if treatment strategies specifically targeting these complications, including preventive aspects, may improve the outcomes after SAH.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Long-term complications; Post-stroke outcomes; Social participation; Subarachnoid hemorrhage

MANAGEMENT OF INSUFFICIENT FUNCTIONAL ANTITHROMBOTIC ACTIVITY DURING TREATMENT WITH DIRECT ORAL ANTICOAGULANTS FOR STROKE PREVENTION - Macha, Kosmas; Stoll, Svenja; Siedler, Gabriela; Volbers, Bastian; Strasser, Erwin; Schwab, Stefan; Kallmünzer, Bernd (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Management of Stroke in Patients with Left Ventricular Assist Devices - Giede-Jeppe, Antje; Röder, Sebastian; Macha, Kosmas; Huttner, Hagen; Gerner, Stefan; Fröhlich, Kilian; Heim, Christian; Schwab, Stefan; Kallmünzer, Bernd (Journal of Stroke and Cerebrovascular Diseases, 2020)
Introduction: The number of patients with left ventricular assist devices (LVAD) is rapidly growing in industrialized countries. While cerebrovascular events comprise a significant complication, data on stroke etiology, clinical management and functional outcome are scarce. Methods: Consecutive LVAD patients with ischemic or hemorrhagic stroke receiving treatment at an university stroke center between 2010 and 2018 were included into an institutional registry. Clinical characteristics, causes, management and functional outcome of stroke occurring within this cohort are reported. Acceptable functional outcome was defined as mRS 0-3. Results: N = 30 acute strokes occurred in 20 patients (77% ischemic, 23% hemorrhagic, mean age 57 ± 13 years, 10% female, 8 patients (40%) had more than one event). 87% of all events happened with non-pulsatile devices, on average 9 (IQR 3-22) months after the implantation. All patients used oral anticoagulation with a Vitamin-K antagonist in combination with anti-platelets. The international normalized ratio (INR)-values were outside the therapeutic range in 39% of ischemic strokes and in 57% of hemorrhagic strokes. Ischemic strokes were predominantly of cardioembolic origin (92%) and of mild to moderate clinical severity (median NIHSS 6 (IQR 4-10). None qualified to receive intravenous thrombolysis or intra-arterial endovascular therapy. 61% of IS-patients showed an acceptable functional outcome after three months. 4/7 patients with hemorrhagic stroke received immediate reversal of anticoagulation without any thrombotic complications. Conclusion: The majority of LVAD patients with ischemic stroke had an acceptable functional outcome after three months. Future clinical research is warranted to improve therapeutic strategies for acute care and stroke prevention.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Functional outcome; Intracerebral hemorrhage; Ischemic stroke; Left ventricular assist devices

Mechanical thrombectomy for acute ischemic stroke in COVID-19 patients: multicenter experience in 111 cases - Styczen, Hanna; Maus, Volker; Goertz, Lukas; Koehrmann, Martin; Kleinschnitz, Christoph; Fischer, Sebastian; Moehlenbruch, Markus; Mühlen, Iris; Kallmünzer, Bernd; Dorn, Franziska; Lakghomi, Asadeh; Gawlitza, Matthias; et al. (Journal of Neurointerventional Surgery, 2022)
Background Data on the frequency and outcome of mechanical thrombectomy (MT) for large vessel occlusion (LVO) in patients with COVID-19 is limited. Addressing this subject, we report our multicenter experience. Methods A retrospective cohort study was performed of consecutive acute stroke patients with COVID-19 infection treated with MT at 26 tertiary care centers between January 2020 and November 2021. Baseline demographics, angiographic outcome and clinical outcome evaluated by the modified Rankin Scale (mRS) at discharge and 90 days were noted. Results We identified 111 out of 11 365 (1%) patients with acute or subsided COVID-19 infection who underwent MT due to LVO. Cardioembolic events were the most common etiology for LVO (38.7%). Median baseline National Institutes of Health Stroke Scale score and Alberta Stroke Program Early CT Score were 16 (IQR 11.5-20) and 9 (IQR 7-10), respectively. Successful reperfusion (mTICI >= 2b) was achieved in 97/111 (87.4%) patients and 46/111 (41.4%) patients were reperfused completely. The procedure-related complication rate was 12.6% (14/111). Functional independence was achieved in 20/108 (18.5%) patients at discharge and 14/66 (21.2%) at 90 days follow-up. The in-hospital mortality rate was 30.6% (33/108). In the subgroup analysis, patients with severe acute COVID-19 infection requiring intubation had a mortality rate twice as high as patients with mild or moderate acute COVID-19 infection. Acute respiratory failure requiring ventilation and time interval from symptom onset to groin puncture were independent predictors for an unfavorable outcome in a logistic regression analysis. Conclusion Our study showed a poor clinical outcome and high mortality, especially in patients with severe acute COVID-19 infection undergoing MT due to LVO.
CRIS-Team WoS Importer:2022-04-01

Monitoring of direct oral anticoagulants plasma levels for secondary stroke prevention - Siedler, Gabriela; Macha, Kosmas; Stoll, Svenja; Plechschmidt, Johannes; Wang, Ruihao; Gerner, Stefan; Strasser, Erwin; Schwab, Stefan; Kallmünzer, Bernd (Journal of Thrombosis and Haemostasis, 2022)
Background: Patients with atrial fibrillation have a relevant risk for ischemic stroke despite the recommended use of direct oral anticoagulants (DOAC). The risk correlates with the functional DOAC plasma levels in clinical trials, but the value of their measurement in community use remains undetermined. Objectives: We aim to investigate the clinical implications and the prognostic value of DOAC plasma level measurement during steady state. Methods: In this observational clinical cohort study among patients with ischemic stroke and atrial fibrillation, 397 individuals on oral anticoagulants for secondary stroke prevention were included between 2016 and 2020. The functional DOAC plasma levels were measured during steady state. Early stroke recurrence within 3 months was recorded as the main outcome parameter. Results: Three hundred ninety-seven patients (201 female, mean age 78 [±9] years, median CHA2DS2VASc-Score 6 [interquartile range 5–7]) were included. Mean DOAC plasma trough level was 95.9 (±66.9) ng/ml. A high glomerular filtration rate (GFR) was an independent predictor of lower levels in a multivariate model (R coefficient: −0.174, P =.014). During follow-up, 10 patients (3%) suffered from early ischemic stroke recurrence despite the use of DOAC, while 10 clinically relevant bleeding complications occurred (3%). Ischemic stroke recurrence was associated with numerical lower plasma levels for patients on apixaban and dabigatran after propensity score matching. Conclusions: Monitoring of DOAC plasma levels could help to identify patients with increased risk for stroke recurrence and should be considered for certain subgroups, including patients with high GFR.
CRIS-Team Scopus Importer:2022-03-18
Keywords: atrial fibrillation; cardioembolic stroke; direct oral anticoagulants; ischemic stroke; secondary prevention

Multimodal CT or MRI for IV thrombolysis in ischemic stroke with unknown time of onset - Macha, Kosmas; Hölter, Philip; Siedler, Gabriela; Knott, Michael; Schwab, Stefan; Dörfler, Arnd; Kallmünzer, Bernd; Engelhorn, Tobias (Neurology, 2020)
OBJECTIVE: To investigate differences in procedure times, safety, and efficacy outcomes comparing 2 different protocols to enable thrombolysis in the extended or unknown time window after stroke onset with either multimodal CT or MRI. METHODS: Patients with ischemic stroke in the extended or unknown time window who received IV thrombolysis between January 2011 and May 2019 were identified from an institutional registry. Imaging-based selection was done by multimodal CT or MRI according to institutional treatment algorithms. RESULTS: IV thrombolysis was performed in 100 patients (54.3%) based on multimodal CT imaging and in 84 patients (45.7%) based on MRI. Baseline clinical data, including stroke severity and time from last seen normal to hospital admission, were similar in patients with CT and MRI. Door-to-needle times were shorter in patients with CT-based selection (median [interquartile range] 45 [37-62] minutes vs 75 [59-90] minutes; mean difference [95% confidence interval (CI)] -28 minutes [-35 to -21]). No differences were detected regarding the incidence of symptomatic intracranial hemorrhage (2 [2.0%] vs 4 [4.8%]; adjusted odds ratio [aOR] [95% CI] 0.47 [0.08-2.83]) and favorable outcome at day 90 (25 [33.8%] vs 33 [42.9%]; aOR 0.95 [0.45-2.02]). CONCLUSION: IV thrombolysis in ischemic stroke in the unknown or extended time window appeared safe in CT- and MRI-selected patients, while the use of CT imaging led to faster door-to-needle times. CLASSIFICATION OF EVIDENCE: This study provides Class IV evidence that for patients with ischemic stroke in the extended or unknown time window, imaging-based selection for IV thrombolysis by multimodal CT compared to MRI led to shorter door-to-needle times.
CRIS-Team Scopus Importer:2020-12-11

Neck cooling induces blood pressure increase and peripheral vasoconstriction in healthy persons - Koehn, Julia; Wang, Ruihao; de Rojas Leal, Carmen; Kallmünzer, Bernd; Winder, Klemens; Köhrmann, Martin; Kollmar, Rainer; Schwab, Stefan; Hilz, Max-Josef (Neurological Sciences, 2020)
Introduction: Noninvasive temperature modulation by localized neck cooling might be desirable in the prehospital phase of acute hypoxic brain injuries. While combined head and neck cooling induces significant discomfort, peripheral vasoconstriction, and blood pressure increase, localized neck cooling more selectively targets blood vessels that supply the brain, spares thermal receptors of the face and skull, and might therefore cause less discomfort cardiovascular side effects compared to head- and neck cooling. The purpose of this study is to assess the effects of noninvasive selective neck cooling on cardiovascular parameters and cerebral blood flow velocity (CBFV). Methods: Eleven healthy persons (6 women, mean age 42 ± 11 years) underwent 90 min of localized dorsal and frontal neck cooling (EMCOOLS Brain.Pad™) without sedation. Before and after cooling onset, and after every 10 min of cooling, we determined rectal, tympanic, and neck skin temperatures. Before and after cooling onset, after 60- and 90-min cooling, we monitored RR intervals (RRI), systolic, diastolic blood pressures (BPsys, BPdia), laser Doppler skin blood flow (SBF) at the index finger pulp, and CBFV at the proximal middle cerebral artery (MCA). We compared values before and during cooling by analysis of variance for repeated measurements with post hoc analysis (significance: p < 0.05). Results: Neck skin temperature dropped significantly by 9.2 ± 4.5 °C (minimum after 40 min), while tympanic temperature decreased by only 0.8 ± 0.4 °C (minimum after 50 min), and rectal temperature by only 0.2 ± 0.3 °C (minimum after 60 min of cooling). Index finger SBF decreased (by 83.4 ± 126.0 PU), BPsys and BPdia increased (by 11.2 ± 13.1 mmHg and 8.0 ± 10.1 mmHg), and heart rate slowed significantly while MCA-CBFV remained unchanged during cooling. Conclusions: While localized neck cooling prominently lowered neck skin temperature, it had little effect on tympanic temperature but significantly increased BP which may have detrimental effects in patients with acute brain injuries.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Blood pressure increase; Cerebral blood flow velocity; Hypothermia; Neck cooling

Neuroanatomical correlates of severe cardiac arrhythmias in acute ischemic stroke - Seifert, Frank; Kallmünzer, Bernd; Gutjahr, Isabell; Breuer, Lorenz; Winder, Klemens; Kaschka, Iris; Kloska, Stephan; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin (Journal of Neurology, 2015)
Neurocardiological interactions can cause severe cardiac arrhythmias in patients with acute ischemic stroke. The relationship between the lesion location in the brain and the occurrence of cardiac arrhythmias is still discussed controversially. The aim of the present study was to correlate the lesion location with the occurrence of cardiac arrhythmias in patients with acute ischemic stroke. Cardiac arrhythmias were systematically assessed in patients with acute ischemic stroke during the first 72 h after admission to a monitored stroke unit. Voxel-based lesion-symptom mapping (VLSM) was used to correlate the lesion location with the occurrence of clinically relevant severe arrhythmias. Overall 150 patients, 56 with right-hemispheric and 94 patients with a left-hemispheric lesion, were eligible to be included in the VLSM study. Severe cardiac arrhythmias were present in 49 of these 150 patients (32.7%). We found a significant association (FDR correction, q < 0.05) between lesions in the right insular, right frontal and right parietal cortex as well as the right amygdala, basal ganglia and thalamus and the occurrence of cardiac arrhythmias. Because left- and right-hemispheric lesions were analyzed separately, the significant findings rely on the 56 patients with right-hemispheric lesions. The data indicate that these areas are involved in central autonomic processing and that right-hemispheric lesions located to these areas are associated with an elevated risk for severe cardiac arrhythmias.
EVALuna2:22355

Neuroanatomic Correlates of Angioedema in stroke patients with thrombolysis - Winder, K.; Kallmünzer, Bernd; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Seifert, F.; Fröhlich, Kilian (EUROPEAN JOURNAL OF NEUROLOGY, 2020)
CRIS-Team WoS Importer:2020-06-16

Oral Anticoagulants in the Oldest Old with Recent Stroke and Atrial Fibrillation - Polymeris, Alexandros A.; Macha, Kosmas; Paciaroni, Maurizio; Wilson, Duncan; Koga, Masatoshi; Cappellari, Manuel; Schaedelin, Sabine; Zietz, Annaelle; Peters, Nils; Seiffge, David J.; Haupenthal, David; Gaßmann, Luise; et al. (Annals of Neurology, 2021)
Objective To investigate the safety and effectiveness of direct oral anticoagulants (DOAC) versus vitamin K antagonists (VKA) after recent stroke in patients with atrial fibrillation (AF) aged >= 85 years. Methods Individual patient data analysis from seven prospective stroke cohorts. We compared DOAC versus VKA treatment among patients with AF and recent stroke (<3 months) aged >= 85 versus <85 years. Primary outcome was the composite of recurrent stroke, intracranial hemorrhage (ICH) and all-cause death. We used simple, adjusted, and weighted Cox regression to account for confounders. We calculated the net benefit of DOAC versus VKA by balancing stroke reduction against the weighted ICH risk. Results In total, 5,984 of 6,267 (95.5%) patients were eligible for analysis. Of those, 1,380 (23%) were aged >= 85 years and 3,688 (62%) received a DOAC. During 6,874 patient-years follow-up, the impact of anticoagulant type (DOAC versus VKA) on the hazard for the composite outcome did not differ between patients aged >= 85 (HR >= 85y = 0.65, 95%-CI [0.52, 0.81]) and < 85 years (HR<85y = 0.79, 95%-CI [0.66, 0.95]) in simple (p(interaction) = 0.129), adjusted (p(interaction) = 0.094) or weighted (p(interaction) = 0.512) models. Analyses on recurrent stroke, ICH and death separately were consistent with the primary analysis, as were sensitivity analyses using age dichotomized at 90 years and as a continuous variable. DOAC had a similar net clinical benefit in patients aged >= 85 (+1.73 to +2.66) and < 85 years (+1.90 to +3.36 events/100 patient-years for ICH-weights 1.5 to 3.1). Interpretation The favorable profile of DOAC over VKA in patients with AF and recent stroke was maintained in the oldest old. ANN NEUROL 2021
CRIS-Team WoS Importer:2021-12-10

Pearls & Oy-sters: Moyamoya Vasculopathy and Its Association With Congenital Heart Disease - Osterloh, Justus; Heim, Christian; Siedler, Gabriela; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Neurology, 2021)
CRIS-Team Scopus Importer:2021-06-25

Peripheral pulse measurement after ischemic stroke: A feasibility study - Kallmünzer, Bernd; Bobinger, Tobias; Kahl, Nicolas; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Marquardt, Lars; Schwab, Stefan; Köhrmann, Martin (Neurology, 2014)
To investigate feasibility and diagnostic accuracy of measurement of the peripheral pulse (MPP) at the radial artery as a simple, noninvasive screening tool for paroxysmal atrial fibrillation (pAF) in patients after acute ischemic stroke.Two hundred fifty-six patients with acute ischemic stroke and the patients' relatives at a tertiary stroke center were prospectively included. Participants were instructed for characteristics of atrial fibrillation (AF) in MPP using standardized educational material. Measurements of participants as well as a health care professional were then compared with simultaneous blinded ECG to evaluate diagnostic accuracy parameters.MPP by the health care professional or patients' relatives had a diagnostic sensitivity of 96.5% and 76.5%, respectively, with 94.0% and 92.9% specificity for the detection of AF. Self-measurements were reliably performed by 89.1% of competent patients with a diagnostic sensitivity of 54.1% and 96.2% specificity. False-positive results were limited to 6 cases (2.7%) with a positive predictive value of 76.9% and a negative predictive value of 90.0%.With a low rate of false-positive results, MPP offers an easy, ubiquitously available, noninvasive, first-step screening tool to guide ECG diagnostics for pAF after ischemic stroke. The data warrant a prospective trial evaluating the efficacy of MPP-guided ECG diagnostics in secondary prevention after stroke, which is now underway.This study provides Class I evidence that MPP by patients or relatives accurately distinguishes AF from normal heart rhythm as compared with continuous ECG.
EVALuna2:22299

PERIPHERAL PULSE MEASUREMENTS FOR THE DETECTION OF SILENT ATRIAL FIBRILLATION: RESULTS FROM THE PROSPECTIVE, CONTROLLED TRIAL "KNOW YOUR PULSE POST STROKE" - Kallmünzer, Bernd; Macha, Kosmas; Wang, Ruihao; Siedler, Gabriela; Stoll, Svenja; Marsch, Armin; Gerner, Stefan; Winder, Klemens; Koehn, J.; Schwab, Stefan; Koehrmann, M. (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Posterior circulation ischemic stroke not involving the brainstem is associated with cardiovascular autonomic dysfunction - Wang, Ruihao; Kohrmann, Martin; Kollmar, Rainer; Köhn, Julia; Schwab, Stefan; Kallmünzer, Bernd; Hilz, Max-Josef (European Journal of Neurology, 2022)
Background and purpose Ischemic stroke may induce cardiovascular autonomic dysfunction, but most previous studies have included patients with anterior circulation ischemic stroke or brainstem stroke. It remains unclear whether posterior circulation ischemic stroke (PCIS) without brainstem involvement also compromises cardiovascular autonomic modulation (CAM). Therefore, we aimed to assess CAM in PCIS patients with and without brainstem involvement. Methods In four subgroups of 61 PCIS patients (14 occipital lobe, 16 thalamic, 12 cerebellar, and 19 brainstem strokes) and 30 healthy controls, we recorded RR intervals (RRIs), systolic (SBP) and diastolic blood pressure (DBP), and respiration at supine rest during the first week after stroke onset. We calculated parameters reflecting total CAM (RRI-standard deviation [RRI-SD], RRI-total powers), predominantly sympathetic CAM (RRI-low-frequency [LF] powers and SBP-LF powers] and parasympathetic CAM (root mean square of successive RRI differences [RMSSD], RRI-high-frequency [HF] powers), sympathetic-parasympathetic balance (RRI-LF/HF ratios), and baroreflex sensitivity (BRS). Values were compared among the four PCIS groups and controls using one-way ANOVA Kruskal-Wallis tests, with post-hoc analyses. Significance was assumed for p < 0.05. Results In each PCIS subgroup, values for RRI, RRI-SD, RMSSD, RRI-HF powers, and BRS were significantly lower, while SBP-LF powers were higher than in the controls. Only in patients with occipital lobe stroke were RRI-LF/HF ratios significantly higher than in controls. Otherwise, autonomic variables did not differ among the four PCIS subgroups. Conclusions During the first week after stroke onset, our PCIS patients with occipital lobe, thalamic, cerebellar, or brainstem strokes all had reduced cardiovagal modulation, compromised baroreflex, and increased peripheral sympathetic modulation. The RRI-LF/HF ratios suggest that sympathetic predominance is slightly more prominent after occipital lobe stroke. PCIS may trigger cardiovascular autonomic dysfunction even without brainstem involvement.
CRIS-Team WoS Importer:2022-06-24

Practical "1-2-3-4-Day" Rule for Starting Direct Oral Anticoagulants After Ischemic Stroke With Atrial Fibrillation: Combined Hospital-Based Cohort Study - Kimura, Shunsuke; Toyoda, Kazunori; Yoshimura, Sohei; Minematsu, Kazuo; Yasaka, Masahiro; Paciaroni, Maurizio; Werring, David J.; Yamagami, Hiroshi; Nagao, Takehiko; Yoshimura, Shinichi; Polymeris, Alexandros; Zietz, Annaelle; et al. (Stroke, 2022)
Background: The "1-3-6-12-day rule" for starting direct oral anticoagulants (DOACs) in patients with nonvalvular atrial fibrillation after acute ischemic stroke or transient ischemic attack recommends timings that may be later than used in clinical practice. We investigated more practical optimal timing of DOAC initiation according to stroke severity. Methods: The combined data of prospective registries in Japan, Stroke Acute Management with Urgent Risk-factor Assessment and Improvement-nonvalvular atrial fibrillation (September 2011 to March 2014) and RELAXED (February 2014 to April 2016) were used. Patients were divided into transient ischemic attack and 3 stroke subgroups by the National Institutes of Health Stroke Scale score: mild (0-7), moderate (8-15), and severe (>= 16). The early treatment group was defined as patients starting DOACs earlier than the median initiation day in each subgroup. Outcomes included a composite of recurrent stroke or systemic embolism, ischemic stroke, and severe bleeding within 90 days. Six European prospective registries were used for validation. Results: In the 1797 derivation cohort patients, DOACs were started at median 2 days after transient ischemic attack and 3, 4, and 5 days after mild, moderate, and severe strokes, respectively. Stroke or systemic embolism was less common in Early Group (n=785)-initiating DOACS within 1, 2, 3, and 4 days, respectively-than Late Group (n=1012) (1.9% versus 3.9%; adjusted hazard ratio, 0.50 [95% CI, 0.27-0.89]), as was ischemic stroke (1.7% versus 3.2%, 0.54 [0.27-0.999]). Major bleeding was similarly common in the 2 groups (0.8% versus 1.0%). On validation, both ischemic stroke (2.4% versus 2.2%) and intracranial hemorrhage (0.2% versus 0.6%) were similarly common in Early (n=547) and Late (n=1483) Groups defined using derivation data. Conclusions: In Japanese and European populations, early DOAC initiation within 1, 2, 3, or 4 days according to stroke severity seemed to be feasible to decrease the risk of recurrent stroke or systemic embolism and no increase in major bleeding. These findings support ongoing randomized trials to better establish the optimal timing of DOAC initiation.
CRIS-Team WoS Importer:2022-05-13

Prevalence and impact on outcome of electrocardiographic early repolarization patterns among stroke patients: a prospective observational study - Bobinger, Tobias; Kallmünzer, Bernd; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Clinical Research in Cardiology, 2015)
Early repolarization pattern (ER) gained attention as a risk factor for ventricular arrhythmia and sudden cardiac death in the general population. While electrocardiographic abnormalities are frequent findings in stroke patients, data on ER pattern in this population are lacking.We assessed the prevalence of ER pattern in consecutive acute stroke patients at a tertiary stroke center. Functional outcome after 90 days was analyzed to determine the effect of an ER pattern on mortality. Multivariate logistic regression analysis was used to identify factors associated with an ER pattern.Out of 1141 consecutive stroke patients 771 patients remained for analysis after application of exclusion criteria. ER was observed in 62 (8.04%) patients. ER was more prevalent among subjects with intracerebral and subarachnoidal hemorrhage (13.0%) than among patients with ischemic stroke (7.0%; p = 0.024). Multiple regression analysis revealed QRS-duration (OR 0.972 95% CI 0.950-0.994, p = 0.012), QT-duration (OR 1.009, 95% CI 1.004-1.014, p = 0.001) and mechanical ventilation on admission (OR 0.320, 95% CI 0.136-0.752, p = 0.009) as independent predictors for ER. Overall ER on admission was not associated with increased mortality at 3-month follow-up (ER 11.3% vs. non-ER 9.2%; p = 0.582).ER is frequently found among patients with acute cerebrovascular events and is more prevalent in patients with hemorrhagic compared to ischemic events. Our study yields no evidence that ER is associated with worse outcome or mortality after stroke.
EVALuna2:12024

Recommendations for the organization of the teleconsultation service in a telestroke network - Wiestler, Hanni; Zickler, Philipp; Erdur, Hebun; Abu-Mugheisib, Mazen; Kallmünzer, Bernd; Klingner, Caroline; Müller-Barna, Peter; Hubert, Gordian; Gumbinger, Christoph; Worthmann, Hans (Neurological Research and Practice, 2024)
Telestroke networks aim to improve acute stroke care within their catchment area. Through a teleconsultation service, the network centers provide support to network hospitals that lack continuous neurological expertise for acute stroke management decisions. Although the importance of telemedical treatment in stroke care is steadily increasing, so far no standards exist for the organization of the teleconsultation service in networks. To ensure a high-level of quality for all processes and measures concerning telemedical stroke treatment, the commission for telemedical stroke care of the German Stroke Society (Deutsche Schlaganfall-Gesellschaft, DSG) created the following recommendations on how to organize a teleconsultation service within a telestroke network. The recommendations are the result of an adjustment process between the authors and include guidance on requirements, qualifications, processes and quality management within the teleconsultation service.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Acute stroke; Recommendations; Teleconsultation service; Telemedicine; Telestroke network

Reliability and limitations of automated arrhythmia detection in telemetric monitoring after stroke - Kurka, Natalia; Bobinger, Tobias; Kallmünzer, Bernd; Koehn, Julia; Schellinger, Peter D.; Schwab, Stefan; Köhrmann, Martin (Stroke, 2015)
Guidelines recommend continuous ECG monitoring in patients with cerebrovascular events. Studies on intensive care units (ICU) demonstrated high sensitivity but high rates of false alarms of monitoring systems resulting in desensitization of medical personnel potentially endangering patient safety. Data on patients with acute stroke are lacking.One-hundred fifty-one consecutive patients with acute cerebrovascular events were prospectively included. Automatically identified arrhythmia events were analyzed by manual ECG analysis. Muting of alarms was registered. Sensitivity was evaluated by beat-to-beat analysis of the entire recorded ECG data in a subset of patients. Ethics approval was obtained by University of Erlangen-Nuremberg.A total of 4809.5 hours of ECG registration and 22 509 alarms were analyzed. The automated detection algorithm missed no events but the overall rate of false alarms was 27.4%. Only 0.6% of all alarms indicated acute life-threatening events and 91.4% of these alarms were incorrect. Transient muting of acoustic alarms was observed in 20.5% patients.Continuous ECG monitoring using automated arrhythmia detection is highly sensitive in acute stroke. However, high rates of false alarms and alarms without direct therapeutic consequence cause desensitization of personnel. Therefore, acoustic alarms may be limited to life-threatening events but standardized manual evaluation of all alarms should complement automated systems to identify clinically relevant arrhythmias.
EVALuna2:22266

STROKE CARE PERFORMANCE MEASURES DURING THE COVID-19 PANDEMIC - OVER THE WAVES - Gaßmann, Luise; Haupenthal, David; Kallmünzer, Bernd; Köhn, Julia; Schwab, Stefan; Kuramatsu, Joji (INTERNATIONAL JOURNAL OF STROKE, 2022)
CRIS-Team WoS Importer:2022-11-18

The anesthetic approach for endovascular recanalization therapy depends on the lesion site in acute ischemic stroke - Fröhlich, Kilian; Siedler, Gabriela; Stoll, Svenja; Macha, Kosmas; Kinfe, Thomas Mehari; Dörfler, Arnd; Eisenhut, Felix; Engelhorn, Tobias; Hölter, Philip; Lang, Stefan; Mühlen, Iris; Schmidt, Manuel; et al. (Neuroradiology, 2021)
Purpose Endovascular therapy (EVT) of large-vessel occlusion in acute ischemic stroke (AIS) may be performed in general anesthesia (GA) or conscious sedation (CS). We intended to determine the contribution of ischemic cerebral lesion sites on the physician's decision between GA and CS using voxel-based lesion symptom mapping (VLSM). Methods In a prospective local database, we sought patients with documented AIS and EVT. Age, stroke severity, lesion volume, vigilance, and aphasia scores were compared between EVT patients with GA and CS. The ischemic lesions were analyzed on CT or MRI scans and transformed into stereotaxic space. We determined the lesion overlap and assessed whether GA or CS is associated with specific cerebral lesion sites using the voxel-wise Liebermeister test. Results One hundred seventy-nine patients with AIS and EVT were included in the analysis. The VLSM analysis yielded associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas. Stroke severity and lesion volume were significantly higher in the GA group. The prevalence of aphasia and aphasia severity was significantly higher and parameters of vigilance lower in the GA group. Conclusions The VLSM analysis showed associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas including the thalamus that are known to cause neurologic deficits, such as aphasia or compromised vigilance, in AIS-patients with EVT. Our data suggest that higher disability, clinical impairment due to neurological deficits like aphasia, or reduced alertness of affected patients may influence the physician's decision on using GA in EVT.
CRIS-Team WoS Importer:2021-07-23

Therapeutic hypothermia for acute ischaemic stroke. Results of a European multicentre, randomised, phase III clinical trial - Van Der Worp, H. Bart; Macleod, Malcolm R.; Bath, Philip M. W.; Bathula, Raj; Christensen, Hanne; Colam, Bridget; Cordonnier, Charlotte; Demotes-Mainard, Jacques; Durand-Zaleski, Isabelle; Gluud, Christian; Jakobsen, Janus Christian; Kallmünzer, Bernd; et al. (European Stroke Journal, 2019)
Introduction We assessed whether modest systemic cooling started within 6 hours of symptom onset improves functional outcome at three months in awake patients with acute ischaemic stroke. Patients and methods In this European randomised open-label clinical trial with blinded outcome assessment, adult patients with acute ischaemic stroke were randomised to cooling to a target body temperature of 34.0-35.0 degrees C, started within 6 h after stroke onset and maintained for 12 or 24 h , versus standard treatment. The primary outcome was the score on the modified Rankin Scale at 91 days, as analysed with ordinal logistic regression. Results The trial was stopped after inclusion of 98 of the originally intended 1500 patients because of slow recruitment and cessation of funding. Forty-nine patients were randomised to hypothermia versus 49 to standard treatment. Four patients were lost to follow-up. Of patients randomised to hypothermia, 15 (31%) achieved the predefined cooling targets. The primary outcome did not differ between the groups (odds ratio for good outcome, 1.01; 95% confidence interval, 0.48-2.13; p = 0.97). The number of patients with one or more serious adverse events did not differ between groups (relative risk, 1.22; 95% confidence interval, 0.65-1.94; p = 0.52). Discussion In this trial, cooling to a target of 34.0-35.0 degrees C and maintaining this for 12 or 24 h was not feasible in the majority of patients. The final sample was underpowered to detect clinically relevant differences in outcomes. Conclusion Before new trials are launched, the feasibility of cooling needs to be improved.
CRIS-Team WoS Importer:2019-10-01

Treatment escalation in patients not responding to pharmacotherapy, psychotherapy, and electro-convulsive therapy: experiences from a novel regimen using intravenous S-ketamine as add-on therapy in treatment-resistant depression - Kallmünzer, Bernd; Volbers, Bastian; Karthaus, Anne; Tektas, Ozan Yueksel; Kornhuber, Johannes; Mueller, Helge H. (Journal of Neural Transmission, 2016)
A lack of response despite maximum therapy is common in patients fulfilling criteria of treatment-resistant depression. Therefore, innovative strategies for treatment escalation are warranted. Here, we report the clinical experiences associated with a novel therapeutic regimen combining electroconvulsive therapy and repeated intravenous S-ketamine treatment in three patients. The combined therapy was feasible and had no serious side effects. All patients responded to the new treatment option. The augmentative effect of sub-anesthetic S-ketamine on ECT is discussed.
EVALuna2:22270

Uncertainty-aware deep learning for trustworthy prediction of long-term outcome after endovascular thrombectomy - Martín Vicario, Celia; Rodriguez Salas, Dalia; Maier, Andreas; Hock, Stefan; Kuramatsu, Joji; Kallmünzer, Bernd; Thamm, Florian; Taubmann, Oliver; Ditt, Hendrik; Schwab, Stefan; Dörfler, Arnd; Mühlen, Iris (Scientific Reports, 2024)
Acute ischemic stroke (AIS) is a leading global cause of mortality and morbidity. Improving long-term outcome predictions after thrombectomy can enhance treatment quality by supporting clinical decision-making. With the advent of interpretable deep learning methods in recent years, it is now possible to develop trustworthy, high-performing prediction models. This study introduces an uncertainty-aware, graph deep learning model that predicts endovascular thrombectomy outcomes using clinical features and imaging biomarkers. The model targets long-term functional outcomes, defined by the three-month modified Rankin Score (mRS), and mortality rates. A sample of 220 AIS patients in the anterior circulation who underwent endovascular thrombectomy (EVT) was included, with 81 (37%) demonstrating good outcomes (mRS≤2). The performance of the different algorithms evaluated was comparable, with the maximum validation under the curve (AUC) reaching 0.87 using graph convolutional networks (GCN) for mRS prediction and 0.86 using fully connected networks (FCN) for mortality prediction. Moderate performance was obtained at admission (AUC of 0.76 using GCN), which improved to 0.84 post-thrombectomy and to 0.89 a day after stroke. Reliable uncertainty prediction of the model could be demonstrated.
CRIS-Team Scopus Importer:2024-05-17

Value of Flat-detector Computed Tomography Angiography with Intravenous Contrast Media Injection in the Evaluation and Treatment of Acutely Ruptured Aneurysms of the AcomA complex: A Single Center Experience in 15 Cases - Rösch, Julie; Lang, Stefan; Gölitz, Philipp; Kallmünzer, Bernd; Roessler, Karl; Dörfler, Arnd; Struffert, Tobias (Clinical Neuroradiology, 2018)
Objective To illustrate the added value of flat-detector computed tomography angiography with intravenous contrast media injection (intravenous FDCTA) in the evaluation of complex A1/A2/AcomA aneurysms. Patients and Methods We retrospectively reviewed 15patients with ruptured aneurysms. In each patient, an intravenous FDCTA was performed and its diagnostic value investigated. Results In all patients, FDCTA contributed relevant additional information concerning the anatomy of the A1/A2/AcomA complex and the relationship of the aneurysm neck to these vascular structures, which could not be gained by 2D- and 3D-DSA, and changed the management in 33% of the patients (5 out of 15). In an additional 5cases, knowledge of the detailed anatomy was helpful to plan the exact stent position. Conclusion In case of complex A1/A2/AcomA aneurysms, intravenous FDCTA is an effective option to visualize the exact location of the aneurysm neck and the relationship between the aneurysm and the adjacent vessels. Thus, it is of significant added value in the precise planning of atherapeutic strategy.
EVALuna2:34934